Polyester film, film laminate using same, and method for producing polyester film

By controlling the formation of diethylene glycol during chemical recycling, adjusting the molar percentage of terephthalic acid, ethylene glycol and diethylene glycol in the polyester film, the problem of degradation of mechanical properties and adhesive strength of the polyester film is solved, and a polyester film with high bonding and stability is achieved.

CN119731233APending Publication Date: 2025-03-28TOYOBO CO LTD

Patent Information

Application Number
CN202380059993.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-17
Filing Date
2023-08-16
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The polyester film made of polyethylene terephthalate obtained by chemical recovery has problems of degradation in terms of mechanical properties and bonding strength.

Method used

By inhibiting the formation of diethylene glycol during chemical recovery, the mole percentage of terephthalic acid, ethylene glycol and diethylene glycol in the polyester film is controlled to ensure high fit and stability.

Benefits of technology

While maintaining high bonding properties, it is possible to suppress the decline in physical properties and adhesive strength of the polyester film, ensuring the stability and applicability of the polyester film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005272322350000131
    Figure BDA0005272322350000131
  • Figure BDA0005272322350000141
    Figure BDA0005272322350000141
  • Figure BDA0005272322350000151
    Figure BDA0005272322350000151
Patent Text Reader

Abstract

The purpose of the present invention is to provide: a polyethylene terephthalate resin which can be obtained using, as a raw material, polyethylene terephthalate obtained from BHET obtained by chemical recovery; to produce a polyester film or the like which has stable characteristics and is suitable for use as a base material film for various laminates while ensuring high adhesion, while suppressing degradation of physical properties and degradation of adhesive force, and which can be further stably produced. The present invention pertains to a polyester film containing, as a starting material resin, a polyethylene terephthalate obtained by polycondensing a starting material containing a polyester resin decomposition component bis (2-hydroxyethyl) terephthalate, the polyethylene terephthalate satisfying the following (a) to (c). (a) the amount of the terephthalic acid component structural unit relative to the total polycarboxylic acid component structural unit in the polyethylene terephthalate is from 98.0 mol% to 99.98 mol% (inclusive); (b) the amount of ethylene glycol constituent units in the polyethylene terephthalate relative to the total polyol constituent units is 97.5 mol% or more and 99.3 mol% or less; and (c) the amount of diethylene glycol constituent units in the polyethylene terephthalate relative to the total amount of polyol constituent units is 0.7-2.5 mol%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyester film using a polyester resin obtained by polycondensing bis(2-hydroxyethyl)terephthalate obtained by chemical recovery, a film laminate using the same, and a method for producing the polyester film. Background Art

[0002] Polyester films are widely used as packaging and industrial parts because they are excellent in mechanical strength, chemical stability, heat resistance, and moisture resistance, and can also improve transparency, are inexpensive, and have a stable supply.

[0003] The most commonly used polyester film is polyethylene terephthalate, which is mainly a polycondensate of terephthalic acid and ethylene glycol. Terephthalic acid and ethylene glycol are produced from petroleum, which is a fossil fuel. In recent years, in order to reduce carbon dioxide emissions and reduce environmental burdens, the recycling of products derived from fossil fuels has been promoted. In polyester, not only mechanical recycling of crushing products and remelting them is being put into practical use, but also chemical recycling (chemical recycling) of decomposing polyester to the monomer level and re-condensing them as raw materials is also being put into practical use.

[0004] In polyester films, research is also underway to use polyethylene terephthalate chemically recycled from PET bottles for beverages, polyester fibers for clothing, etc., in order to reduce environmental burden (e.g., Patent Document 1). Even such films that address environmental burdens are required to be used for the same purposes as non-recycled resins and have the same properties. Prior art literature Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2022-28868 Summary of the invention Problem that the invention aims to solve

[0006] The inventors of the present invention have studied the application of polyester films formed using PET obtained from chemically recycled BHET in various applications. It is known that although the polyester films formed using PET obtained from chemically recycled BHET have good adhesion to other raw materials such as adhesives and coating agents, there are cases where the mechanical properties are reduced (for example, the heat shrinkage rate increases and the rigidity decreases) or the adhesive strength decreases.

[0007] In more detail, the following matters were further understood. In chemically recycled BHET, it is difficult to avoid the mixing of isophthalic acid components and other copolymer components derived from bottles, and diethylene glycol, a by-product when polymerizing PET, a constituent raw material of chemically recycled BHET, is also mixed.

[0008] In addition, since diethylene glycol is also produced in the polycondensation process of chemically recovered BHET, the amount of diethylene glycol in PET produced from chemically recovered BHET will further increase.

[0009] By changing the amount of these copolymer components, the crystals of the polyester film become slightly disordered, and the adhesion is improved. On the other hand, when the copolymer components are increased, the crystal disorder increases, resulting in a decrease in film properties (for example, an increase in heat shrinkage and a decrease in rigidity).

[0010] The object of the present invention is to provide a polyester film, a polyester film laminate and a method for producing a polyester film, wherein the polyester film uses polyethylene terephthalate made from BHET obtained by chemical recycling as a raw material, suppresses the decrease in physical properties and adhesiveness while ensuring high adhesion, has stable characteristics, and can be suitably used as a base film for various laminates. A more preferred object of the present invention is to provide a polyester film, a polyester film laminate, and a method for producing a polyester film, wherein the polyester film uses polyethylene terephthalate made from BHET obtained by chemical recycling as a raw material, and has reduced heat shrinkage (especially heat shrinkage in the MD direction) and rigidity while ensuring high adhesion. Means of solving the problem

[0011] The present inventors have found that the above-mentioned problems can be solved by suppressing the generation of diethylene glycol in the production of PET using chemically recycled BHET to an appropriate range, thereby completing the present invention.

[0012] That is, the present invention consists of the following structures.

[0013] [Item 1] A polyester film characterized by containing polyethylene terephthalate as a raw material resin, wherein the polyethylene terephthalate is obtained by polycondensing a raw material containing bis(2-hydroxyethyl) terephthalate as a decomposition component of a polyester resin, and the polyethylene terephthalate satisfies the following (a) to (c): (a) the amount of terephthalic acid component structural units in the polyethylene terephthalate relative to the total polycarboxylic acid component structural units is 98.0 mol% or more and 99.98 mol% or less; (b) the amount of the ethylene glycol component structural units in the polyethylene terephthalate relative to the total polyol component structural units is 97.5 mol% or more and 99.3 mol% or less; (c) The amount of the diethylene glycol component structural units in the polyethylene terephthalate is 0.7 mol% or more and 2.5 mol% or less based on the total polyol component structural units.

[0014] [Item 2] The polyester film according to item 1, wherein the polyethylene terephthalate further satisfies (d), (d) The amount of the isophthalic acid component structural units in the polyethylene terephthalate is 0.02 mol% or more and 2.0 mol% or less based on the total polycarboxylic acid component structural units.

[0015] [Item 3] According to the polyester film of item 1 or 2, the value of [the total amount of polycarboxylic acid component structural units in the polyethylene terephthalate + the total amount of polyol component structural units in the polyethylene terephthalate - the amount of terephthalic acid component structural units in the polyethylene terephthalate - the amount of ethylene glycol component structural units in the polyethylene terephthalate] is less than 4.1 mol%.

[0016] [Item 4] The polyester film according to Item 1 or 2, further comprising an alkali agent.

[0017] [Item 5] The polyester film according to Item 1, which is a void-containing film.

[0018] [Item 6] The polyester film according to Item 1, which is a heat-shrinkable film.

[0019] [Item 7] The polyester film according to Item 1, wherein the polyethylene terephthalate contains an aluminum compound and a phosphorus compound.

[0020] [Item 8] A polyester film, characterized in that it contains polyethylene terephthalate as a raw material resin, wherein the polyethylene terephthalate is obtained by polycondensing a raw material containing bis(2-hydroxyethyl) terephthalate as a decomposition component of a polyester resin, and the polyester constituting the film satisfies the following (a') to (c'), (a') the amount of terephthalic acid component structural units in the polyester constituting the film is 98.0 mol% or more and 99.98 mol% or less relative to the total polycarboxylic acid component structural units; (b') the amount of ethylene glycol component structural units in the polyester constituting the film is 97.5 mol% or more and 99.3 mol% or less relative to the total polyol component structural units; (c′) The amount of diethylene glycol component structural units in the polyester constituting the film is 0.7 mol% or more and 2.5 mol% or less based on the total polyol component structural units.

[0021] [Item 9] The polyester film according to item 8, wherein the polyester constituting the film further satisfies (d'), (d′) In the polyester constituting the film, the amount of the isophthalic acid component structural units relative to the total polycarboxylic acid component structural units is 0.02 mol% or more and 2.0 mol% or less.

[0022] [Item 10] The polyester film according to Item 8, wherein the polyester constituting the film contains an aluminum compound and a phosphorus compound.

[0023] [Item 11] A polyester film laminate comprising the polyester film according to any one of items 1 to 10.

[0024] [Item 12] The polyester film laminate according to item 11, comprising one or more selected from the group consisting of a printed layer, a radiation-curing resin layer, an inorganic layer, a shielding layer, a resin film layer different from polyester, a heat seal layer, a release layer and an adhesive layer.

[0025] [Item 13] A method for producing a polyester film, characterized in that it comprises the following steps (A) and (B): (A) a step of polymerizing bis(2-hydroxyethyl) terephthalate having the following properties (e), (f) and (g) obtained by depolymerizing polyethylene terephthalate to obtain polyethylene terephthalate; and (B) a step of producing a film using the polyethylene terephthalate resin obtained by polymerization as a raw material resin, (e) the amount of terephthalic acid component structural units in bis(2-hydroxyethyl)terephthalate relative to the total polycarboxylic acid component structural units is 98 mol% or more and 99.98 mol% or less; (f) the amount of ethylene glycol component structural units in bis(2-hydroxyethyl) terephthalate relative to the total polyol component structural units is 98.7 mol% or more and 99.9 mol% or less; (g) The amount of the diethylene glycol component structural unit in bis(2-hydroxyethyl)terephthalate is 0.1 mol% or more and 2.6 mol% or less based on the total polycarboxylic acid component structural units.

[0026] [Item 14] According to the method for producing a polyester film according to item 13, the bis(2-hydroxyethyl)terephthalate further satisfies the following property (h), (h) The amount of the isophthalic acid component structural units in bis(2-hydroxyethyl)terephthalate is 0.02 mol% or more and 2.0 mol% or less based on the total polycarboxylic acid component structural units.

[0027] [Item 15] The method for producing a polyester film according to Item 13 or 14, wherein the step (A) includes adding an alkali agent.

[0028] [Item 16] The method for producing a polyester film according to item 13 or 14, wherein the step (A) includes adding a catalyst containing one or more selected from the group consisting of antimony compounds, germanium compounds and aluminum compounds.

[0029] [Item 17] The method for producing a polyester film according to Item 13 or 14, wherein the step (A) is performed within 200 minutes.

[0030] [Item 18] The method for producing a polyester film according to item 13 or 14, wherein the polyethylene terephthalate satisfies the following (a) to (c), (a) the amount of terephthalic acid component structural units in the polyethylene terephthalate relative to the total polycarboxylic acid component structural units is 98.0 mol% or more and 99.98 mol% or less; (b) the amount of the ethylene glycol component structural units in the polyethylene terephthalate relative to the total polyol component structural units is 97.5 mol% or more and 99.3 mol% or less; (c) The amount of the diethylene glycol component structural units in the polyethylene terephthalate is 0.7 mol% or more and 2.5 mol% or less based on the total polyol component structural units.

[0031] [Item 19] According to the method for producing a polyester film according to item 18, the polyethylene terephthalate further satisfies (d), (d) The amount of the isophthalic acid component structural units in the polyethylene terephthalate is 0.02 mol% or more and 2.0 mol% or less based on the total polycarboxylic acid component structural units.

[0032] [Item 20] According to the method for producing a polyester film described in item 18 or 19, the value of [the total amount of polycarboxylic acid component structural units in the polyethylene terephthalate + the total amount of polyol component structural units in the polyethylene terephthalate - the amount of terephthalic acid component structural units in the polyethylene terephthalate - the amount of ethylene glycol component structural units in the polyethylene terephthalate] is less than 4.1 mol%. Effects of the Invention

[0033] According to the present invention, polyethylene terephthalate obtained from BHET obtained by chemical recycling can be used as a raw material to produce a polyester film having stable characteristics while ensuring high adhesion and suppressing the reduction of physical properties and adhesiveness. The polyester film of the present invention can be used as a base film for various laminates. According to a more preferred embodiment of the present invention, polyethylene terephthalate obtained from BHET obtained by chemical recycling can be used as a raw material, which has reduced heat shrinkage (particularly heat shrinkage in the MD direction) and rigidity while ensuring high adhesion. DETAILED DESCRIPTION

[0034] Method for producing polyester film The method for producing the polyester film of the present invention preferably comprises the following steps (A) and (B). (A) a step of polymerizing bis(2-hydroxyethyl) terephthalate having the following properties (e), (f) and (g) obtained by depolymerizing polyethylene terephthalate to obtain polyethylene terephthalate; and (B) a step of producing a film using the polyethylene terephthalate resin obtained by polymerization as a raw material resin, (e) the amount of terephthalic acid component structural units in bis(2-hydroxyethyl)terephthalate relative to the total polycarboxylic acid component structural units is 98 mol% or more and 99.98 mol% or less; (f) the amount of ethylene glycol component structural units in bis(2-hydroxyethyl) terephthalate relative to the total polyol component structural units is 98.7 mol% or more and 99.9 mol% or less; (g) The amount of the diethylene glycol component structural unit in bis(2-hydroxyethyl)terephthalate is 0.1 mol% or more and 2.6 mol% or less based on the total polycarboxylic acid component structural units.

[0035] Preferably, the above bis(2-hydroxyethyl)terephthalate further satisfies (h), (h) The amount of the isophthalic acid component structural units in bis(2-hydroxyethyl)terephthalate is 0.02 mol% or more and 2.0 mol% or less based on the total polycarboxylic acid component structural units.

[0036] The present invention provides a method for producing a polyester film using polyethylene terephthalate obtained by polycondensing bis(2-hydroxyethyl) terephthalate obtained by chemical recovery, a polyester film, and a polyester film laminate. In the following, bis(2-hydroxyethyl)terephthalate may be simply referred to as BHET, and bis(2-hydroxyethyl)terephthalate obtained by chemical recovery may be simply referred to as chemically recovered BHET or CR-BHET.

[0037] First, chemically recycled BHET and polyethylene terephthalate obtained by polycondensation thereof are described. In addition, polyethylene terephthalate obtained by polycondensation of chemically recycled BHET is sometimes referred to as chemically recycled PET or CR-PET. In addition, polyethylene terephthalate is sometimes referred to as PET.

[0038] The step (A) is a step of obtaining polyethylene terephthalate by polymerizing bis(2-hydroxyethyl) terephthalate having the following properties (e), (f), and (g) obtained by depolymerizing polyethylene terephthalate. Chemical recycling BHET is a substance obtained by heating PET in the presence of ethylene glycol to depolymerize. The PET constituting the raw material is preferably a used PET, for example, PET bottles recycled on the street, containers such as trays, fibers, products, discarded products before selecting products in manufacturing, products that are not shipped to the market as B-grade products, ear parts held during stretching film, scraps of incisions, molded products returned due to complaints, etc. These PET constituting the raw materials can be substances derived from petroleum such as terephthalic acid and ethylene glycol, or substances derived from biomass. In addition, it can also be a molded product recovered mechanically. In addition, it can also be a mixture of these PETs.

[0039] The PET constituting the raw material is usually preferably used in the depolymerization step after being pulverized, washed, and freed of foreign matter. During depolymerization, ethylene glycol, sodium hydroxide, potassium hydroxide and other alkaline compounds are added to PET, and depolymerization is carried out by heating. The obtained reactant is filtered and decolorized as needed, and the remaining ethylene glycol is further distilled off to obtain a crude BHET product. The crude BHET product can be purified by distillation, crystallization, etc. to prepare chemically recovered BHET of a purity suitable for polycondensation.

[0040] BHET obtained by chemical recovery can remove pigments, dyes, catalysts, metal ions, etc., but chemically recovered BHET may also contain linear dimers or polymers thereof. In addition, it may also contain mono(2-hydroxyethyl)terephthalate, terephthalic acid, ethylene glycol, etc.

[0041] The total of the acid value and hydroxyl value of chemically recovered BHET is preferably 6500 eq / ton or more and 9500 eq / ton or less, more preferably 7000 eq / ton or more and 9000 eq / ton or less, and further preferably 7500 eq / ton or more and 8500 eq / ton or less. By controlling within the above range, productivity can be ensured while maintaining sufficient purity.

[0042] Chemically recovered BHET may also contain dicarboxylic acid components other than terephthalic acid components as polycarboxylic acid components, and glycol components other than ethylene glycol as polyol components. Examples of dicarboxylic acid components other than terephthalic acid components include isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, adipic acid, sebacic acid, cyclohexane dicarboxylic acid, and the like, and examples of glycol components other than ethylene glycol include diethylene glycol, neopentyl glycol, cyclohexanedimethanol, trimethylene glycol, tetramethylene glycol, ethylene glycol or propylene glycol adducts of bisphenol A, and ethylene glycol or propylene glycol adducts of bisphenol S, and the like.

[0043] (e) bis(2-hydroxyethyl) terephthalate From the viewpoint of reducing the heat shrinkage and the sense of rigidity, when the total polycarboxylic acid component structural units are 100 mol%, the amount of the terephthalic acid component structural units in the polycarboxylic acid component contained in the chemically recovered BHET is preferably 98.0 mol% or more and 99.98 mol% or less, second preferably 98.0 mol% or more and 99.95 mol% or less, more preferably more than 98.0 mol% and 99.9 mol% or less, further preferably 98.3 mol% or more and 99.85 mol% or less, and still more preferably 98.3 mol% or more and 99.8 mol% or less. From the viewpoint of further reducing the amounts of isophthalic acid and diethylene glycol structural units, the amount of terephthalic acid component structural units in bis(2-hydroxyethyl)terephthalate relative to the total polycarboxylic acid component structural units is preferably 98.5 mol% to 99.95 mol%, more preferably 98.8 mol% to 99.9 mol%, further preferably 99.0 mol% to 99.85 mol%, and even more preferably 99.2 mol% to 99.8 mol%.

[0044] As described above, chemically recycled BHET preferably includes depolymerized products of PET including recycled products from the market. Although recycled PET from the market may contain components other than PET in order to adjust crystallinity, physical properties, etc., it is not preferred to select only pure PET from recycled products or to purify BHET to a level where acid components other than terephthalic acid cannot be detected from a cost perspective.

[0045] Bis(2-hydroxyethyl)terephthalate (h) As the polycarboxylic acid component other than terephthalic acid contained in the chemically recovered BHET, isophthalic acid is often contained. From the viewpoint of reducing the heat shrinkage rate and the sense of rigidity, when the total polycarboxylic acid component structural units are 100 mol%, the amount of the isophthalic acid component structural units in bis(2-hydroxyethyl) terephthalate relative to the total polycarboxylic acid component structural units is preferably 0.02 mol% to 2 mol%, more preferably 0.05 mol% to less than 2 mol%, further preferably 0.1 mol% to 1.7 mol%, further preferably 0.15 mol% to 1.7 mol%, particularly preferably 0.2 mol% to 1.7 mol%. From the viewpoint of further reducing the amount of isophthalic acid component structural units contained, the amount of isophthalic acid component structural units in bis(2-hydroxyethyl)terephthalate relative to the total polycarboxylic acid component structural units is preferably 0.02 mol% to 1.5 mol%, more preferably 0.05 mol% to 1.2 mol%, further preferably 0.1 mol% to 1.0 mol%, and even more preferably 0.15 mol% to 0.8 mol%.

[0046] (f) Bis(2-hydroxyethyl) terephthalate From the viewpoint of reducing the heat shrinkage rate and the sense of rigidity, when the total polyol component structural units are 100 mol%, the amount of the ethylene glycol component structural units in the diol component as the polyol component contained in the chemically recovered BHET is preferably 98.7 mol% or more and 99.9 mol% or less, more preferably 99.0 mol% or more and 99.8 mol% or less, further preferably 99.2 mol% or more and 99.75 mol% or less, and particularly preferably 99.2 mol% or more and 99.7 mol% or less. From the viewpoint of further reducing the amount of diethylene glycol component structural units in the total polyol component structural units, the amount of ethylene glycol component structural units in bis(2-hydroxyethyl) terephthalate relative to the total polyol component structural units is preferably 99.3 mol% or more and 99.9 mol% or less, and more preferably 99.4 mol% or more and 99.8 mol% or less.

[0047] When the total polyol component is 100 mol%, the amount of free ethylene glycol in the ethylene glycol component contained in the chemically recovered BHET is preferably 1.5 mol% or less, more preferably 1.2 mol% or less, further preferably 1.0 mol% or less, particularly preferably 0.8 mol% or less, and most preferably 0.6 mol% or less. The amount of free ethylene glycol is preferably infinitely close to 0 mol%, more preferably 0.01 mol% or more, or 0.02 mol% or more.

[0048] As described above, from the perspective of cost, it is not preferred to select only pure PET from the recyclate or to purify BHET to a level where diol components other than ethylene glycol cannot be detected. In addition, diethylene glycol is produced as a side reaction in the production process of PET, so this is difficult to avoid.

[0049] Bis(2-hydroxyethyl)terephthalate (g) Even among the glycol components other than ethylene glycol contained in the chemically recovered BHET, diethylene glycol is often contained. From the viewpoint of reducing the heat shrinkage rate and the sense of rigidity, when the total polyol component structural units are 100 mol%, the amount of the diethylene glycol component structural units in bis(2-hydroxyethyl) terephthalate relative to the total polyol component structural units is preferably 0.1 mol% to 2.6 mol%, more preferably 0.3 mol% to 2.0 mol%, further preferably 0.5 mol% to 1.7 mol%, and particularly preferably 0.6 mol% to 1.7 mol%. From the viewpoint of further reducing the amount of diethylene glycol component structural units contained in BHET, the amount of diethylene glycol component structural units in bis(2-hydroxyethyl)terephthalate relative to the total polyol component structural units is preferably 0.1 mol% to 1.4 mol%, more preferably 0.3 mol% to 1.4 mol%, further preferably 0.5 mol% to 1.2 mol%, and even more preferably 0.6 mol% to 1.2 mol%.

[0050] The above-mentioned terephthalic acid component, isophthalic acid component, ethylene glycol component, and diethylene glycol component are values ​​including components existing as monomers in the chemically recovered BHET.

[0051] In order to reduce the amount of diethylene glycol contained in the chemically recovered BHET, it is preferred to appropriately adjust the amount and time of the added ethylene glycol when depolymerizing PET. When the amount of ethylene glycol is small, there is a situation where sufficient transesterification with diethylene glycol in PET does not occur. In addition, when the amount of ethylene glycol is too much, there is a situation where diethylene glycol is generated from ethylene glycol and mixed into the chemically recovered BHET. The amount of ethylene glycol added is preferably 5 to 7 times the mass of PET. When the depolymerization time is short, there is a case where sufficient transesterification with diethylene glycol in PET does not occur. When the time is long, there is a case where diethylene glycol is generated from ethylene glycol and mixed into the chemical recovery BHET. The depolymerization time is preferably 3 to 10 hours. It is preferred to crush PET into an appropriate size in advance so that the depolymerization can be completed at an appropriate time.

[0052] Chemical recovery BHET has the situation that the PET constituting the raw material is different, and the amount of copolymerization component is often different. In addition, in the manufacture of PET, it is difficult to completely avoid the generation of diethylene glycol, because the difference of manufacturing conditions and the difference of equipment state, the generation amount of diethylene glycol is also different. Due to these factors, the composition of the obtained PET changes, and when exceeding a certain range, there is a worry that the characteristics of the film using PET will deteriorate. In order to make a polyester film with stable quality, it is preferred that the copolymerization component control of the chemical recovery polyester resin used for the film is set within a specific range, so even if it is to widen the selection range of the manufacturing conditions of chemical recovery PET, in addition, in order to obtain chemical recovery PET well in terms of productivity, it is also preferred to make the dicarboxylic acid component structural unit amount and the diol component structural unit amount of chemical recovery BHET be a certain range.

[0053] For example, when using PET bottles, PET is often copolymerized with a small amount of isophthalic acid and diethylene glycol. In order to set the chemically recycled BHET used to manufacture PET to the above range, it is preferred not only to select the chemically recycled BHET within the above range, but also to adjust the usage ratio of PET constituting the raw material of depolymerization, or to mix multiple chemically recycled BHETs so that they meet the above range, etc., to adjust and select them to be within the range of (e), (f), and (g).

[0054] In addition, since the copolymerized glycol components such as diethylene glycol have a higher boiling point than ethylene glycol and are less likely to volatilize during polycondensation, they are easily mixed into the polyester resin. It is preferable to determine the range of the amount of the glycol components other than ethylene glycol in consideration of these factors.

[0055] When the amount of the terephthalic acid component structural unit in the above-mentioned bis(2-hydroxyethyl) terephthalate relative to 100 mol% of the total polycarboxylic acid component structural unit is TPA(b) mol%; when the amount of the ethylene glycol component structural unit in the bis(2-hydroxyethyl) terephthalate relative to 100 mol% of the total polyol component structural unit is EG(b) mol%, The value of (100-TPA(b))+(100-EG(b))×2 is preferably 0.15 mol% to 4 mol%, more preferably 0.3 mol% to 3.5 mol%, further preferably 0.3 mol% to 3 mol%, particularly preferably 0.5 mol% to 2.8 mol%. By setting the above range, the obtained film can have stable adhesion and adhesive force, and can also highly maintain the mechanical strength (preferably rigidity) and heat resistance (preferably reduced thermal shrinkage) of the film. Furthermore, the selection range of the manufacturing conditions of chemically recycled PET can be widened, and chemically recycled PET can be obtained with good productivity.

[0056] Chemical recovery BHET and copolymerization components as required etc. can be added to the reaction vessel, and a catalyst is further added, and a polycondensation reaction is carried out while the generated diol is removed to the outside of the system in a rectification tower under reduced pressure, thereby obtaining chemical recovery PET. The polycondensation can be batch-wise or continuous. When it is continuous, it is preferably a multi-tank method in which more than two polycondensation tanks are connected.

[0057] (catalyst) Any catalyst commonly used can be used without limitation as the catalyst, and examples thereof include antimony compounds, titanium compounds, germanium compounds, aluminum compounds, and composite catalysts of aluminum compounds and phosphorus compounds. In the method for producing the polyester film of the present invention, the step (A) preferably includes a step of adding a catalyst containing one or more selected from the group consisting of antimony compounds, germanium compounds, and aluminum compounds, and more preferably includes a step of adding a catalyst containing an antimony compound, an antimony compound and a germanium compound or an aluminum compound.

[0058] As the germanium compound, germanium dioxide, germanium tetrachloride, etc. can be mentioned, among which germanium dioxide is preferred. As the residual amount of germanium element in the manufactured PET, the content (mass basis) of the germanium compound is preferably 10 ppm or more and 200 ppm or less, more preferably 20 ppm or more and 150 ppm or less, and further preferably 30 ppm or more and 100 ppm or less.

[0059] Titanium compounds include tetra-n-propyl titanate, tetra-isopropyl titanate, tetra-n-butyl titanate, tetra-isobutyl titanate, tetra-tert-butyl titanate, tetracyclohexyl titanate, tetraphenyl titanate, titanium oxalate, phthalic acid titanate, trimellitic acid titanate, pyromellitic acid titanate, etc. Among these, tetra-n-butyloxy titanate and trimellitic acid titanate are preferred. As the residual amount of titanium element in the produced PET, the content (by mass) of the titanium compound is preferably 1 ppm or more and 30 ppm or less, more preferably 2 ppm or more and 25 ppm or less, and further preferably 3 ppm or more and 20 ppm or less.

[0060] Examples of the antimony compound include antimony trioxide, antimony pentaoxide, antimony acetate, and antimony glycoside, among which antimony trioxide is preferred. As the residual amount of antimony element in the produced PET, the content (by mass) of the antimony compound is preferably 50 ppm or more and 350 ppm or less, more preferably 80 ppm or more and 330 ppm or less, further preferably 100 ppm or more and 300 ppm or less, further preferably 100 ppm or more and 250 ppm or less, and particularly preferably 100 ppm or more and 230 ppm or less. The contents of antimony, titanium and germanium can be measured, for example, by the method described in Examples below.

[0061] By setting the amount of the catalyst to an amount above the above, the polycondensation rate can be increased, productivity can be ensured, and the generation of diethylene glycol can be reduced. By setting the amount of the catalyst to an amount below the above, the generation of foreign matter derived from the catalyst can be reduced, transparency can be improved, and a film with less coloration can be obtained, while reducing the molecular weight reduction during molding and the molecular weight reduction of the recycled resin from the film manufacturing process.

[0062] Examples of the aluminum compound and the phosphorus compound include the following.

[0063] (Aluminum compounds) The aluminum compound is not limited as long as it is soluble in the solvent, and known aluminum compounds can be used without limitation. Among these, at least one selected from carboxylates, inorganic acid salts and chelates is preferred. Among these, at least one selected from aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide, basic aluminum chloride and aluminum acetylacetonate is more preferred, at least one selected from aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide, basic aluminum chloride and aluminum acetylacetonate is further preferred, at least one selected from aluminum acetate and basic aluminum acetate is particularly preferred, and basic aluminum acetate is most preferred.

[0064] The content of the aluminum compound, as the content of aluminum element in the chemically recycled PET, is preferably 5 to 70 mass ppm, more preferably 7 to 55 mass ppm, further preferably 10 to 40 mass ppm, and particularly preferably 15 to 30 mass ppm. When the content of aluminum element is less than 5 mass ppm, there is a concern that the polymerization activity cannot be fully exerted. On the other hand, when it exceeds 70 mass ppm, there is a concern that the amount of aluminum-based foreign matter increases.

[0065] In addition, when cost is important, the content of aluminum in chemically recycled PET is preferably 9 to 20 mass ppm, more preferably 9 to 19 mass ppm, further preferably 10 to 17 mass ppm, and particularly preferably 12 to 17 mass ppm. When the content of aluminum is less than 9 mass ppm, there is a concern that the polymerization activity cannot be fully exerted. On the other hand, when it exceeds 20 mass ppm, there is a concern that the amount of aluminum-based foreign matter increases from the relationship with the content of phosphorus described later, and in addition, the cost of the catalyst also increases. When an aluminum compound is used as a catalyst, it is preferred to use at least one selected from the group consisting of compounds of Group 1 elements or Group 2 elements in the periodic table such as lithium, sodium, potassium, beryllium, magnesium, and calcium, or a phosphorus compound. In addition, Group 1 in the periodic table is also called IA or alkali metals, and Group 2 is also called IIA or alkaline earth metals. The content of the aluminum element can be measured, for example, by the method described in Examples below.

[0066] Examples of compounds of these Group 1 elements and Group 2 elements include saturated aliphatic carboxylates of formic acid, acetic acid, propionic acid, butyric acid, oxalic acid, and the like, unsaturated aliphatic carboxylates of acrylic acid, methacrylic acid, and the like, aromatic carboxylates of benzoic acid, and the like, halogen-containing carboxylates of trichloroacetic acid, and the like, hydroxycarboxylates of lactic acid, citric acid, and salicylic acid, and inorganic acid salts of carbonic acid, sulfuric acid, nitric acid, phosphoric acid, phosphonic acid, hydrogen carbonate, hydrogen phosphate, hydrogen sulfide, sulfurous acid, thiosulfuric acid, hydrochloric acid, hydrobromic acid, chloric acid, and bromic acid, and organic sulfonates of 1-propanesulfonic acid, 1-pentanesulfonic acid, and naphthalenesulfonic acid, and organic sulfates of laurylsulfuric acid, and the like, hydrocarbon oxides of methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, and tert-butoxy, and chelates, hydrides, oxides, and hydroxides with acetylacetone, and the like. The amount of these compounds added is preferably 0.1 mol to 7.0 mol, more preferably 0.2 mol to 4.0 mol, further preferably 0.2 mol% to 3.0 mol%, further preferably 0.2 mol% to 2.5 mol%, particularly preferably 0.2 mol% to 1.2 mol%, per 1 ton of the obtained PET, in terms of the amount of the elements. By setting the above range, it is possible to increase the polycondensation rate and ensure productivity while reducing the generation of diethylene glycol, further reducing the generation of foreign matter, and obtaining a film with high transparency and little coloration while reducing the molecular weight drop during molding and the molecular weight drop of the recovered resin from the film manufacturing process.

[0067] (Phosphorus compounds) The phosphorus compound is not particularly limited, but is preferably a phosphonic acid compound or a phosphinic acid compound from the viewpoint of a large effect of improving the catalytic activity. Among these, a phosphonic acid compound is more preferred from the viewpoint of a particularly large effect of improving the catalytic activity.

[0068] Among the above-mentioned phosphorus compounds, phosphorus compounds having a phosphorus element and a phenol structure in the same molecule are preferred. There are no particular limitations as long as the phosphorus compound has a phosphorus element and a phenol structure in the same molecule. From the viewpoint of a greater effect of improving the catalytic activity, one or more compounds selected from the group consisting of phosphonic acid compounds having a phosphorus element and a phenol structure in the same molecule and phosphinic acid compounds having a phosphorus element and a phenol structure in the same molecule are preferred. From the viewpoint of a very large effect of improving the catalytic activity, one or more phosphonic acid compounds having a phosphorus element and a phenol structure in the same molecule are more preferred.

[0069] In addition, examples of phosphorus compounds having a phosphorus element and a phenol structure in the same molecule include: P(=O)R 1 (OR 2 )(OR 3 )、P(=O)R 1 R 4 (OR 2 ) represented by the compound, etc. 1 R represents a hydrocarbon group having 1 to 50 carbon atoms and having a phenol structure, a hydrocarbon group having 1 to 50 carbon atoms and having a substituent selected from the group consisting of a hydroxyl group, a halogen group, an alkoxy group and an amino group, and a phenol structure. 4 R represents hydrogen, a hydrocarbon group having 1 to 50 carbon atoms, or a hydrocarbon group having 1 to 50 carbon atoms having a substituent selected from the group consisting of a hydroxyl group, a halogen group, an alkoxy group, and an amino group. 2 , R 3 Each independently represents hydrogen, a hydrocarbon group having 1 to 50 carbon atoms, or a hydrocarbon group having 1 to 50 carbon atoms having a substituent selected from the group consisting of a hydroxyl group and an alkoxy group. The hydrocarbon group may contain a branched structure, an alicyclic structure such as a cyclohexyl group, or an aromatic ring structure such as a phenyl group or a naphthyl group. 2 and R 4 The ends of the two molecules may be bonded to each other.

[0070] Examples of the phosphorus compound having a phosphorus element and a phenol structure in the same molecule include p-hydroxyphenylphosphonic acid, dimethyl p-hydroxyphenylphosphonate, diethyl p-hydroxyphenylphosphonate, diphenyl p-hydroxyphenylphosphonate, bis(p-hydroxyphenyl)phosphinic acid, methyl bis(p-hydroxyphenyl)phosphinic acid, phenyl bis(p-hydroxyphenyl)phosphinic acid, p-hydroxyphenylphosphinic acid, methyl p-hydroxyphenylphosphinic acid, and phenyl p-hydroxyphenylphosphinic acid.

[0071] As the phosphorus compound having a phosphorus element and a phenol structure in the same molecule, in addition to the compounds exemplified above, there can be mentioned a phosphorus compound having a phosphorus element and a hindered phenol structure (a phenol structure in which an alkyl group having a tertiary carbon (preferably an alkyl group having a tertiary carbon such as a tertiary butyl group or a tertiary hexyl group at the benzyl position; a neopentyl group, etc.) is bonded to one or two ortho positions of a hydroxyl group) in the same molecule, preferably a phosphorus compound having a phosphorus element and a structure of the following (chemical formula A) in the same molecule, and more preferably 3,5-di-tert-butyl-4-hydroxybenzyl dialkylphosphonate represented by the following (chemical formula B). In addition, as the phosphorus compound used for the production of the polyester resin (B), 3,5-di-tert-butyl-4-hydroxybenzyl dialkylphosphonate represented by the following (chemical formula B) is preferred, and in addition, a modified form of 3,5-di-tert-butyl-4-hydroxybenzyl dialkylphosphonate may be included. The details of the modified form will be described later.

[0072] [Chemistry 1]

[0073] (In (chemical formula A), * represents the 1 (OR 2 )(OR 3 ) 1 The atoms of the hydrocarbon group are bonded together.)

[0074] [Chemistry 2]

[0075] (In (chemical formula B), X 1 , X 2 Each represents hydrogen or an alkyl group having 1 to 4 carbon atoms. )

[0076] In this specification, at least one hindered phenol structure can be detected by a P-NMR measurement method of a solution obtained by dissolving a polyester resin in a hexafluoroisopropanol-based solvent. A polyester resin in which a hindered phenol structure is detected is also referred to as a polyester resin "having a hindered phenol structure". That is, chemically recycled PET is preferably a polyester resin produced using a phosphorus compound having a phosphorus element and a hindered phenol structure in the same molecule as a polymerization catalyst. The detection method (P-NMR measurement method) of the hindered phenol structure in PET is described below.

[0077] In the above (chemical formula B), X 1 , X 2 All of them are preferably alkyl groups having 1 to 4 carbon atoms, and more preferably alkyl groups having 1 to 2 carbon atoms. In particular, an ethyl ester having 2 carbon atoms is commercially available as Irganox 1222 (manufactured by BASF Corporation) and is therefore preferred because it is easily available.

[0078] The phosphorus compound is preferably used after heat treatment in a solvent. In addition, the details of the heat treatment are described later. As the phosphorus compound, when using 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester as a phosphorus compound shown in (chemical formula B), in the above-mentioned heat treatment, it is preferred that a part of the 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester as a phosphorus compound shown in (chemical formula B) undergoes structural changes. For example, at least one of the detachment of the tert-butyl group, the hydrolysis of the ethyl ester group, and the hydroxyethyl ester exchange structure (ester exchange structure with ethylene glycol) can be produced. Therefore, in the present invention, as a phosphorus compound, in addition to the 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester shown in (chemical formula B), a phosphorus compound with a structural change can also be contained. In addition, the detachment of the tert-butyl group occurs significantly at high temperatures in the polymerization process.

[0079] Hereinafter, when diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate is used as the phosphorus compound, 9 phosphorus compounds in which a part of diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate undergoes structural changes are shown. The amount of each phosphorus compound undergoing structural changes in the diol solution can be quantified by the P-NMR measurement method.

[0080] [Chemistry 3]

[0081] Therefore, the phosphorus compound in the present invention may include, in addition to 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester, nine modified forms of 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester represented by the above chemical formula.

[0082] When Irganox 1222 is used as the phosphorus compound, the polyester resin may contain 9 types of phosphorus compound residues shown in Table 1 below. When at least one of the 9 types of hindered phenol structures shown in Table 1 is detected by P-NMR measurement, the polyester resin (B) can be said to be a polyester resin produced using a phosphorus compound having a phosphorus element and a hindered phenol structure in the same molecule as a polymerization catalyst. By using a phosphorus compound having a hindered phenol structure, sufficient polymerization activity can be exerted while suppressing the cost of the catalyst.

[0083] [Table 1]

[0084] In the present invention, it is preferred that at least one of the above Chemical Formulas 1, 4 and 7 is contained.

[0085] The content of phosphorus in chemically recycled PET is preferably 5 to 1000 mass ppm, more preferably 10 to 500 mass ppm, further preferably 15 to 200 mass ppm, particularly preferably 20 to 100 mass ppm, and most preferably 30 to 80 mass ppm. When the phosphorus content is less than 5 mass ppm, there is concern that the polymerization activity decreases, the amount of aluminum-based foreign matter increases, and the effect of improving thermal stability decreases. On the other hand, when it exceeds 1000 mass ppm, there is concern that the polymerization activity decreases, the amount of phosphorus compounds added increases, and the catalyst cost increases.

[0086] When cost is further emphasized, the phosphorus content in chemically recycled PET is preferably 13 to 31 mass ppm, more preferably 15 to 29 mass ppm, and even more preferably 16 to 28 mass ppm. When the phosphorus content is less than 13 mass ppm, there is a concern that the polymerization activity decreases and the amount of aluminum-based foreign matter increases. On the other hand, when it exceeds 31 mass ppm, there is a concern that the polymerization activity decreases, the amount of phosphorus compounds added increases, and the catalyst cost increases. The phosphorus content can be measured, for example, by the method described in Examples below.

[0087] The molar ratio of phosphorus to aluminum in chemically recycled PET is preferably 1.00 to 5.00, more preferably 1.10 to 4.00, further preferably 1.20 to 3.50, and particularly preferably 1.25 to 3.00. As described above, the aluminum and phosphorus in chemically recycled PET are derived from aluminum compounds and phosphorus compounds used as polymerization catalysts, respectively. By using these aluminum compounds and phosphorus compounds in a specific ratio, a complex with catalytic activity can be functionally formed in the polymerization system to exert sufficient polymerization activity. In addition, compared to polyester resins produced using catalysts such as antimony catalysts, resins produced using polymerization catalysts composed of aluminum compounds and phosphorus compounds have increased catalyst costs (increased manufacturing costs), but by using aluminum compounds and phosphorus compounds in a specific ratio, it is possible to suppress the cost of the catalyst while exerting sufficient polymerization activity. When the residual molar ratio of phosphorus to aluminum is less than 1.00, there is a concern that thermal stability and thermal oxidation stability will decrease, and there is a concern that the amount of aluminum-based foreign matter will increase. On the other hand, when the residual molar ratio of phosphorus element to aluminum element exceeds 5.00, the amount of phosphorus compound added increases too much, so there is a concern that the catalyst cost may increase. When further focusing on the components, the residual molar ratio of phosphorus element to aluminum element is preferably 1.32 to 1.80, and more preferably 1.38 to 1.68.

[0088] As described above, in chemically recycled BHET, the copolymer components vary from batch to batch. Therefore, in order to stabilize the film quality, it is preferred not only to set the copolymer components of chemically recycled BHET to a specific range, but also to reduce the generation of diethylene glycol as much as possible when using chemically recycled BHET to manufacture PET. When the amount of diethylene glycol produced is large, due to the synergistic effect with the copolymerization component contained in the chemically recovered BHET, even if the conditions of the polycondensation step are slightly changed, the characteristics of the obtained polyester film may change greatly. In order to suppress the amount of diethylene glycol produced, for example, the following method is preferably adopted.

[0089] In the method for producing a polyester film of the present invention, when an acid component is further added to the chemically recovered BHET, the step (A) preferably includes a step of performing an esterification reaction of the acid component in a relatively short time. Specifically, for example, under the condition of ethylene glycol reflux, the esterification reaction is carried out while the water or alcohol generated by the reaction is removed to the outside of the system in a distillation tower. The temperature of the esterification reaction is preferably 240 to 280°C, more preferably 245 to 275°C, and the pressure is preferably 0.05 to 0.2 MPa. The esterification reaction is preferably within 180 minutes, more preferably within 160 minutes, further preferably within 140 minutes, particularly preferably within 120 minutes, and most preferably within 100 minutes. In addition, at this time, the acid component relative to the amount of ethylene glycol added is preferably set to 2.2 molar times or less, and more preferably set to 2.1 molar times or less.

[0090] Furthermore, in the method for producing a polyester film of the present invention, it is preferred that the step (A) be performed within 200 minutes. By carrying out the polycondensation reaction in a short time, the amount of diethylene glycol produced can be suppressed. While adjusting the temperature and the degree of reduced pressure so that the degree of polymerization rises in a relatively short time, polycondensation is carried out. In the early stage of polycondensation, the temperature is preferably 260-270°C, and the pressure is preferably 0.01MPa-0.001MPa. The pressure is reduced while the temperature is slowly raised, and finally the temperature is preferably 270-285°C and the pressure is preferably 0.00002-0.000005MPa. During the period from reaching the above temperature to the end, the time of the polycondensation reaction is preferably within 200 minutes, more preferably within 180 minutes, further preferably within 160 minutes, particularly preferably within 140 minutes, and most preferably within 120 minutes. In addition, it is preferred to quickly carry out the heating from the start of loading chemical recovery BHET to the initial temperature. In order to shorten the heating time, it is preferred to improve the surface area of ​​the contents, while the size and shape of the reaction vessel are suitably adjusted, and the amount of chemical recovery BHET input is also suitably adjusted. In addition, it is preferred to stir fully. In order to rationalize the amount of the added polycondensation catalyst to obtain a high polymerization rate and improve surface renewal, it is also important to stir fully. When the amount of catalyst is too much, foreign matter is formed, and there is a situation where the transparency of the film decreases or the defects increase. Depending on the purpose of the film, it is preferred to increase the amount of catalyst within the scope of allowing these problems. Considering the appropriate amount of catalyst and stirring, the time of the polycondensation reaction is preferably more than 30 minutes, more preferably more than 45 minutes.

[0091] In the method for producing a polyester film of the present invention, step (A) preferably includes a step of adding an alkali agent. During the esterification reaction and the polycondensation reaction, the amount of diethylene glycol produced can be suppressed by adding an alkali agent. Examples of the alkaline agent include tertiary amines such as triethylamine, tri-n-butylamine and benzyldimethylamine, quaternary ammonium hydroxides such as tetraethylammonium hydroxide, tetra-n-butylammonium hydroxide and trimethylbenzylammonium hydroxide, carbonates such as lithium carbonate, sodium carbonate and potassium carbonate (preferably alkali metal carbonates), and acetates such as sodium acetate (preferably alkali metal acetates). Among them, the alkaline agent is preferably a tertiary amine, more preferably triethylamine or tri-n-butylamine, and still more preferably triethylamine.

[0092] The amount of the alkali agent is preferably 0.01 mol % to 2 mol %, more preferably 0.05 mol % to 1.5 mol %, and further preferably 0.1 mol % to 1 mol %, based on the total polycarboxylic acid components.

[0093] Polyethylene terephthalate The polyethylene terephthalate obtained by the method for producing a polyester film of the present invention preferably satisfies the following (a) to (c). (a) the amount of terephthalic acid component structural units in the polyethylene terephthalate relative to the total polycarboxylic acid component structural units is 98.0 mol% or more and 99.98 mol% or less; (b) the amount of the ethylene glycol component structural units in the polyethylene terephthalate relative to the total polyol component structural units is 97.5 mol% or more and 99.3 mol% or less; (c) The amount of the diethylene glycol component structural units in the polyethylene terephthalate is 0.7 mol% or more and 2.5 mol% or less based on the total polyol component structural units.

[0094] The polyethylene terephthalate preferably further satisfies (d). (d) The amount of the isophthalic acid component structural units in the polyethylene terephthalate is 0.02 mol% or more and 2.0 mol% or less based on the total polycarboxylic acid component structural units. The above (a), (b), (c) and (d) are as described below.

[0095] The polyester film of the present invention is characterized in that it contains polyethylene terephthalate as a raw material resin, wherein the polyethylene terephthalate is obtained by polycondensing a raw material containing bis(2-hydroxyethyl) terephthalate which is a decomposition component of a polyester resin, and the polyethylene terephthalate contains predetermined amounts of terephthalic acid component structural units, ethylene glycol component structural units, and diethylene glycol component structural units. The polyester film of the present invention is a chemical raw material polyester film formed from BHET, a decomposition component of PET, and preferably reduces heat shrinkage and improves rigidity by inhibiting the generation of diethylene glycol.

[0096] Polyethylene terephthalate (a) The amount of the terephthalic acid component structural units in the polyethylene terephthalate relative to the total polycarboxylic acid component structural units is preferably 98.0 mol% or more and 99.98 mol% or less, less preferably 98.1 mol% or more and 99.95 mol% or less, more preferably 98.2 mol% or more and 99.9 mol% or less, further preferably 98.3 mol% or more and 99.85 mol% or less, and still more preferably 98.3 mol% or more and 99.8 mol% or less. From the viewpoint of improving the rigidity, the amount of the terephthalic acid component structural units in the polyethylene terephthalate is preferably 98.5 mol% or more and 99.98 mol% or less, more preferably 98.8 mol% or more and 99.95 mol% or less, further preferably 99 mol% or more and 99.9 mol% or less, and still more preferably 99.2 mol% or more and 99.85 mol% or less, based on the total polycarboxylic acid component structural units.

[0097] Polyethylene terephthalate (d) The amount of the isophthalic acid component structural units in the polyethylene terephthalate relative to the total polycarboxylic acid component structural units is preferably 0.02 mol% to 2 mol%, more preferably 0.05 mol% to 1.9 mol%, further preferably 0.1 mol% to 1.8 mol%, particularly preferably 0.15 mol% to 1.7 mol%, and most preferably 0.2 mol% to 1.7 mol%. From the viewpoint of improving the rigidity, the amount of the isophthalic acid component structural units in ethylene terephthalate is preferably 0.02 mol% to 1.5 mol% based on the total polycarboxylic acid component structural units, more preferably 0.05 mol% to 1.2 mol%, further preferably 0.1 mol% to 1 mol%, further preferably 0.15 mol% to 0.8 mol%.

[0098] Polyethylene terephthalate (b) The amount of the ethylene glycol component structural units in the polyethylene terephthalate relative to the total polyol component structural units is preferably 97.5 mol% to 99.3 mol%, less preferably 97.6 mol% to 99.1 mol%, more preferably 97.7 mol% to 99 mol%, further preferably 97.7 mol% to 98.9 mol%, and even more preferably 97.8 mol% to 98.8 mol%. From the viewpoint of reducing the amount of diethylene glycol structural units, the amount of ethylene glycol component structural units in polyethylene terephthalate relative to the total polycarboxylic acid component structural units is preferably 97.9 mol% or more and 99.3 mol% or less, more preferably 97.9 mol% or more and 99.1 mol% or less, further preferably 98 mol% or more and 99 mol% or less, and still more preferably 98 mol% or more and 98.9 mol% or less.

[0099] Polyethylene terephthalate (c) The amount of the diethylene glycol component structural unit in the polyethylene terephthalate relative to the total polyol component structural units is preferably 0.7 mol% to 2.5 mol%, less preferably 0.8 mol% to 2.4 mol%, more preferably 0.9 mol% to 2.3 mol%, further preferably 1 mol% to 2.3 mol%, particularly preferably 1.1 mol% to 2.2 mol%, and most preferably 1.2 mol% to 1.8 mol%. From the viewpoint of reducing the amount of component structural units other than terephthalic acid and ethylene glycol in the film, the amount of diethylene glycol component structural units in polyethylene terephthalate relative to the total polycarboxylic acid component structural units is preferably 0.7 mol% or more and 2.1 mol% or less, more preferably 0.9 mol% or more and 2.0 mol% or less, further preferably 1 mol% or more and 1.9 mol% or less, and still more preferably 1.1 mol% or more and 1.8 mol% or less.

[0100] In the method for producing a polyester film of the present invention, it is preferred that the value of [the total amount of polycarboxylic acid component structural units in the polyethylene terephthalate + the total amount of polyol component structural units in the polyethylene terephthalate - the amount of terephthalic acid component structural units in the polyethylene terephthalate - the amount of ethylene glycol component structural units in the polyethylene terephthalate] is less than 4.1 mol%. When this value satisfies the above, the heat shrinkage is reduced and the rigidity is improved. This value is preferably greater than 0.8 mol% and less than 4.1 mol%, more preferably greater than 0.9 mol% and less than 4 mol%, further preferably greater than 1 mol% and less than 3.5 mol%, further preferably greater than 1.2 mol% and less than 3.2 mol%, particularly preferably greater than 1.2 mol% and less than 3.0 mol%, and most preferably greater than 1.2 mol% and less than 2.8 mol%.

[0101] The above values ​​can be expressed as follows. When the amount of the terephthalic acid component structural unit relative to the total polycarboxylic acid component structural unit of the above-mentioned chemically recycled PET is TPA(r); the amount of the ethylene glycol component structural unit relative to the total polyol component structural unit of the chemically recycled PET is EG(r), The value of 200-TPA(r)-EG(r) is preferably greater than 0.8 mol% and less than 4.1 mol%, more preferably greater than 0.9 mol% and less than 4 mol%, further preferably greater than 1 mol% and less than 3.5 mol%, further preferably greater than 1.2 mol% and less than 3.2 mol%, particularly preferably greater than 1.2 mol% and less than 3.0 mol%, and most preferably greater than 1.2 mol% and less than 2.8 mol%.

[0102] By setting the composition of the chemically recycled PET to be within the above range, when a film is produced, the heat shrinkage rate can be reduced and the rigidity can be improved.

[0103] The intrinsic viscosity of chemically recycled PET is preferably 0.5 dL / g or more and 0.8 dL / g or less, more preferably 0.55 dL / g or more and 0.77 dL / g or less, and further preferably 0.58 dL / g or more and 0.75 dL / g or less. By setting the above range, the strength and film-making stability of the film can be ensured. In order to obtain chemically recycled PET with high intrinsic viscosity, it is preferred to carry out solid phase polymerization after melt polymerization.

[0104] The acid value of chemically recycled PET is preferably 0 equivalents / ton or more and 60 equivalents / ton or less, more preferably 1 equivalents / ton or more and 55 equivalents / ton or less, further preferably 2 equivalents / ton or more and 50 equivalents / ton or less, particularly preferably 3 equivalents / ton or more and 45 equivalents / ton or less, and most preferably 4 equivalents / ton or more and 40 equivalents / ton or less. Although solid phase polymerization is preferably performed to reduce the acid value, when solid phase polymerization is not performed, the acid value of PET is preferably 15 equivalents / ton or more and 60 equivalents / ton or less, more preferably 20 equivalents / ton or more and 55 equivalents / ton or less, further preferably 23 equivalents / ton or more and 50 equivalents / ton or less, and particularly preferably 25 equivalents / ton or more and 45 equivalents / ton or less. By setting the acid value in the above range, the productivity of PET can be ensured, and the acid value of the obtained film can be set in a suitable range. In order to set the acid value in the above range, it is preferred to adopt a method such as maintaining the above appropriate temperature and reduced pressure during polycondensation, replacing the reaction container with an inert gas such as nitrogen during polycondensation, and creating a low oxygen state.

[0105] Next, step (B) is performed. Step (B) is a step of producing a film using the polyethylene terephthalate resin obtained by polymerization as a raw material resin. This process can adopt the existing known technology. As this process, there can be mentioned: melting resin, extruding molten resin, making the extruded resin close to a cooling roller to obtain an unstretched film, using a single shaft or a double shaft to stretch the unstretched film, heat fixing the stretched film, relaxing the stretched film, laminating other layers, etc.

[0106] In the present invention, the chemically recycled PET obtained in this way is used to manufacture a film. In the manufacture of the film, the molten resin is preferably extruded into a sheet-like shape, and after cooling, the obtained unstretched sheet-like object is stretched in at least one direction. In the stretching, a roller stretching method is preferably used when stretching in the longitudinal direction of the film, and a tenter stretching method is preferably used when stretching in the transverse direction. In addition, a tenter can also be used to simultaneously perform longitudinal and transverse biaxial stretching. The stretching temperature is preferably 80 to 130° C., more preferably 85 to 120° C., in both the longitudinal and transverse directions, and can be adjusted within this temperature range in accordance with the desired properties. For the stretching ratio, it is preferred that at least one of the longitudinal and transverse directions as the main stretching directions is 3 to 8 times, more preferably 3.3 to 7 times, and it can be adjusted within this range in combination with the desired properties. The stretching ratio in other directions can also be adjusted by the properties required for the manufactured film. Furthermore, after stretching, heat treatment and relaxation treatment are performed as needed to adjust the thermal shrinkage. The temperature of the heat treatment is preferably above 70°C and below the melting point. For example, when it is only a film of chemically recycled PET, it is preferably 150 to 240°C.

[0107] Polyester film The polyester film of the present invention is a polyester film containing polyethylene terephthalate as a raw material resin, wherein the polyethylene terephthalate is obtained by polycondensing a raw material containing bis(2-hydroxyethyl) terephthalate which is a decomposition component of a polyester resin, and the polyester constituting the film preferably contains a specified amount of a terephthalic acid component structural unit (a'), an ethylene glycol component structural unit (b'), and a diethylene glycol component structural unit (c'). The conditions (a') to (c') satisfied by the polyester constituting the film are as follows. (a') the amount of terephthalic acid component structural units in the polyester constituting the film is 98.0 mol% or more and 99.98 mol% or less relative to the total polycarboxylic acid component structural units; (b') the amount of ethylene glycol component structural units in the polyester constituting the film is 97.5 mol% or more and 99.3 mol% or less relative to the total polyol component structural units; (c′) The amount of diethylene glycol component structural units in the polyester constituting the film is 0.7 mol% or more and 2.5 mol% or less based on the total polyol component structural units. The above-mentioned (a'), (b'), and (c') may be respectively the same as the above-mentioned (a), (b), and (c).

[0108] The polyester constituting the film preferably further satisfies (d'). (d′) The amount of the isophthalic acid component structural units in the polyester constituting the film is 0.02 mol% or more and 2.0 mol% or less based on the total polycarboxylic acid component structural units. The above-mentioned (d') may be the same as the above-mentioned (d). The polyester constituting the film may contain an aluminum compound and a phosphorus compound used as a catalyst. The polyester or polyester film of the present invention preferably further contains an alkali agent.

[0109] The film may further contain a colorant, lubricant particles, an ultraviolet absorber, a melt resistivity adjuster, an antistatic agent, an antioxidant, a heat stabilizer, and the like. The film may be a single-layer structure or a multi-layer structure obtained by coextrusion. In the case of a multi-layer structure, the composition of each layer may be different, such as adding an ultraviolet absorber only to the middle layer and adding a lubricant only to the surface layer.

[0110] In the manufacture of the film, all the raw material PET used may not be chemically recycled PET, but may contain PET made from terephthalic acid and ethylene glycol. In particular, in the manufacture of the film, when adding lubricant particles, resistivity regulators, pigments, ultraviolet absorbers, etc., there is a case where they are mixed as a masterbatch, but it is not necessary to use chemically recycled PET for the PET used in the masterbatch, and it is also possible to pursue economical production by sharing these with ordinary PET films.

[0111] The amount of chemically recycled PET in the raw material PET used is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, particularly preferably 90% by mass or more, and most preferably 95% by mass or more. The amount of chemically recycled PET in 100% by mass of the raw material PET may also be 100% by mass.

[0112] For the film, all raw material resins may not be PET, and may contain copolyester or other resins for the purpose of use. Among the raw material resins of the film, chemically recycled PET is preferably 20% by mass or more, more preferably 40% by mass or more, further preferably 50% by mass or more, further preferably 60% by mass or more, particularly preferably 70% by mass or more, and most preferably 90% by mass or more. However, the most preferred embodiment of the present invention is a film in which the resin constituting the film is substantially composed of only PET. Here, substantially composed of only PET means that the resin component in the state of the film is only PET, and does not contain resin components such as resin particles, inorganic particles and other surface modifiers as lubricants. The PET constituting the film is preferably within the composition range shown in the chemically recycled PET. In addition, the preferred amount of the catalyst is also the same.

[0113] The intrinsic viscosity of the polyester constituting the film is preferably 0.48 dL / g or more and 0.78 dL / g or less, more preferably 0.50 dL / g or more and 0.75 dL / g or less, further preferably 0.53 dL / g or more and 0.72 dL / g or less, and particularly preferably 0.55 dL / g or more and 0.68 dL / g or less. By setting it to the above range, the mechanical strength of the film can be ensured and the productivity can be improved.

[0114] The acid value of the polyester constituting the film is preferably 3 equivalents / ton or more and 65 equivalents / ton or less, more preferably 5 equivalents / ton or more and 60 equivalents / ton or less, further preferably 8 equivalents / ton or more and 55 equivalents / ton or less, and particularly preferably 10 equivalents / ton or more and 50 equivalents / ton or less. When the film is produced using a melt-polymerized polyester, the acid value of the polyester constituting the film is preferably 20 equivalents / ton or more and 65 equivalents / ton or less, more preferably 25 equivalents / ton or more and 60 equivalents / ton or less, further preferably 28 equivalents / ton or more and 55 equivalents / ton or less, and particularly preferably 30 equivalents / ton or more and 50 equivalents / ton or less. By setting it as the said range, the productivity of a film can be ensured, and the time-dependent degradation of a film and the degradation by moist heat can be reduced. In addition, in the use of films that require long-term degradation resistance, such as insulating films such as motor insulating films and solar cell backplane films, the acid value of the polyester constituting the film is preferably greater than 3 equivalents / ton and less than 20 equivalents / ton, more preferably greater than 3 equivalents / ton and less than 15 equivalents / ton, and further preferably greater than 3 equivalents / ton and less than 10 equivalents / ton. When the melting temperature during film production becomes too high, the acid value of the film becomes too high compared to the raw material PET, or the intrinsic viscosity becomes too low. It is preferred to manage the piping and the like to keep the melting state short while maintaining the melting temperature appropriately.

[0115] In the molecular weight distribution curve obtained by gel permeation chromatography (GPC), the area ratio of the region with a molecular weight of 1,000 or less of the polyester constituting the film is preferably 1.9% or more and 5.5% or less of the total peak area, more preferably 2.0% or more and 5.2% or less, further preferably 2.2% or more and 5.0% or less, further preferably 2.4% or more and 4.7% or less, still further preferably 2.6% or more and 4.5% or less, particularly preferably 2.8% or more and 4.5% or less, and most preferably 3.0% or more and 4.5% or less. By setting the content to 5.5% or less, that is, by setting the upper limit of the content of components with a molecular weight of 1,000 or less (i.e., low molecular weight components), the film can be suppressed from having a yellow tint.

[0116] By setting the content to 1.9% or more, that is, by setting a lower limit to the content of the low molecular weight component, it is possible to prevent the stress during film stretching from becoming excessively large, thereby suppressing or reducing film breakage that may occur during stretching.

[0117] In order to make the area ratio of the molecular weight below 1000 within the above range, it is preferred to adjust the molecular weight (intrinsic viscosity) of the polyester resin used for the film; mix a low molecular weight polyester when using a high molecular weight polyester; make the melting temperature of the resin preferably not more than 290°C, more preferably not more than 288°C in the film manufacturing process; shorten the distance of the pipe from the extruder to the die outlet to shorten the time for the polyester to melt, etc. In addition, as a catalyst, it is also preferred to use a composite catalyst of an aluminum compound and a phosphorus compound with excellent thermal stability for the obtained polyester.

[0118] The thickness of the polyester film is preferably 1 to 2000 μm, more preferably 2 to 1000 μm. The thickness can be set to an appropriate range according to the application. For example, if it is for optical use, the representative thickness is 20 to 150 μm; if it is a transfer or release film, the representative thickness is 10 to 100 μm; if it is a general packaging film, the representative thickness is 5 to 50 μm; if it is a thick product such as a tray, the representative thickness is 200 to 1000 μm.

[0119] The polyester film of the present invention preferably has a predetermined heat shrinkage ratio in the MD direction. The heat shrinkage rate in the MD direction of the polyester film is preferably 0% or more and less than 1.8%, more preferably more than 0% and 1.7% or less, further preferably 0.1% or more and 1.6% or less, further preferably 0.2% or more and 1.5% or less, particularly preferably 0.3% or more and 1.4% or less. The heat shrinkage rate in the MD direction can be measured based on JIS C2318 and can be calculated according to the following formula. MD direction heat shrinkage (%) = {(L0 (interval between marking lines set at 200 mm intervals) - L (interval between marking lines after treatment at 150°C for 30 minutes)) / L0 (interval between marking lines set at 200 mm intervals)} × 100

[0120] The polyester film is preferably surface treated in order to improve adhesion with adhesives, coating materials, inks, etc. Examples of the surface treatment include corona treatment, plasma treatment, and flame treatment.

[0121] An easy-adhesive layer may be further provided on the polyester film. The resin used for the easy-adhesive layer can be polyester resin, polyurethane resin, polycarbonate resin, acrylic resin, etc., preferably polyester resin, polyester polyurethane resin, polycarbonate polyurethane resin, acrylic resin. The easy-adhesive layer is preferably cross-linked. As a cross-linking agent, isocyanate compounds, melamine compounds, epoxy resins, oxazoline compounds, etc. can be cited. In addition, adding water-soluble resins such as polyvinyl alcohol is also a useful means for improving the adhesion with the polarizer.

[0122] The adhesive layer can be provided by coating a polyester film with a water-based coating material containing these resins and, if necessary, a crosslinking agent, particles, etc., and then drying the coating material. Examples of the particles include those used for the above-mentioned substrates. The easy-adhesive layer can be provided on the stretched film off-line, but it is preferably provided in-line during the film-making process. When provided in-line, it can be provided before longitudinal stretching or before transverse stretching, but it is preferably applied before transverse stretching, and dried and cross-linked in the preheating, heating, and heat treatment process using a tenter. In addition, when the in-line coating is performed before longitudinal stretching using a roller, it is preferably dried in a vertical dryer after coating and then introduced into the stretching roller. The coating amount of the adhesive layer is preferably 0.01 to 1.0 g / m 2 , more preferably 0.03 to 0.5 g / m 2 .

[0123] The present invention includes a polyester film laminate containing the polyester film. The film of the present invention is preferably used as a polyester film laminate by utilizing its excellent adhesiveness. The polyester film laminate preferably has one or more selected from the group consisting of a printing layer, a radiation-cured resin layer, an inorganic layer, a barrier layer, a resin film layer different from polyester, a heat seal layer, a release layer, and an adhesive layer.

[0124] (Application of polyester film) The polyester film can be used for various purposes as exemplified below. In addition, examples of laminated bodies combined with the purposes are also described interspersed. Release film: For example, a release film used in the manufacturing process of articles such as ceramic green sheets and resin solution films can be mentioned. For example, it can also be a release film attached to the following adhesive layer laminate. The thickness of the substrate of the release film is preferably 10 to 150 μm, and more preferably 20 to 100 μm. Transfer film: For example, a transfer film is used to transfer a thin film provided on a film, such as a metal foil, a printed pattern layer, a liquid crystal compound retardation layer, a liquid crystal compound polarizer, etc., to another article. The release film or transfer film may further include a release layer made of fluorine-based resin, silicone-based resin, acrylic acid containing a long-chain alkyl group, polyolefin, etc. The thickness of the base material of the release film is preferably 3 to 100 μm, more preferably 5 to 50 μm.

[0125] · Protective film: For example, a polarizing plate protective film, a surface protective film of an image display device, a rear surface protective film, a solar cell back sheet, etc. may be mentioned. Process protective film: Examples include protective films used to prevent contamination and damage during or after the manufacture of products such as polarizing plates, lenses, prism sheets, image display panels, cosmetic panels, and transparent resin plates until use. In these applications, an adhesive layer may also be provided. For example, a rubber-based, acrylic-based, silicone-based, urethane-based adhesive layer may also be provided on the protective film. In addition, in the case of a permanent protective film such as a solar cell back sheet, it may also be a material that is attached to an object by an adhesive. The thickness of the protective film is preferably 20 to 200 μm, and more preferably 30 to 160 μm.

[0126] Optical film: Examples thereof include lens sheet substrates, prism sheet substrates, nylon printed film substrates, diffusion sheet substrates, scattering prevention films, polarizer protective films, and transparent conductive film substrates. In lens, prism sheet, and nanoimprinting, a layer of an acrylic compound provided on a polyester film is brought into contact with a mold and irradiated with radiation to cure it, thereby forming a pattern. In the surface protection film of the image display device, the polarizer protection film, etc., a hard coating layer, an anti-reflection layer, an anti-reflection layer, an anti-glare layer, etc. can be provided. On the transparent conductive film, a hard coating layer, a refractive index adjustment layer, etc. can be provided. The hard coating layer and the refractive index adjustment layer are preferably radiation-cured resins such as acrylic compounds. As the conductive layer of the transparent conductive film, there can be cited: ITO film, metal etching, mesh of conductive paste, coating layer of metal whiskers, etc. In these uses, the thickness of the film is preferably 20 to 250 μm, more preferably 30 to 200 μm.

[0127] Films for electrical, electronic and communication use: Examples thereof include flexible circuit substrates, cover lay films, carrier tape covers, electronic tag substrates, IC cards, and motor insulation films.

[0128] Printed substrate film: Examples include electrical product labels, advertising labels, and campaign labels. The thickness of the printing base material film is preferably 5 to 100 μm, more preferably 10 to 70 μm.

[0129] · Barrier film: Examples of the barrier layer include barrier films provided with inorganic layers such as metal vapor-deposited layers and metal oxide vapor-deposited layers, and barrier coating layers. The shielding layer has functions such as water vapor barrier and gas barrier. Examples of metal vapor deposition include aluminum, and examples of metal oxides include aluminum oxide, silicon dioxide, aluminum oxide-silicon composite oxide, etc. Examples of barrier coatings include sol-gel coatings, coatings containing inorganic layered compound particles, polyvinyl alcohol coatings, ethylene-vinyl alcohol copolymer coatings, and vinyl chloride coatings. The thickness of the inorganic layer is preferably 1 to 100 nm, more preferably 5 to 50 nm. An anchor coating may be provided between the inorganic layer and the film, and a protective coating may be provided on the inorganic layer. It may also be a composite of an inorganic layer and a barrier coating. The thickness of the protective coating and the barrier coating is preferably 0.1 to 10 μm, more preferably 0.2 to 7 μm. The thickness of the substrate film is preferably 5 to 75 μm, more preferably 7 to 50 μm.

[0130] · Laminated film for packaging: Examples include lamination with nylon film, polypropylene film, etc. Furthermore, a heat seal layer or barrier film may be laminated on the laminated film for packaging. The thickness of the film is preferably 5 to 75 μm, more preferably 7 to 50 μm. · Laminated film for battery packaging: Examples include films for outer packaging of primary batteries such as fuel cells and lithium-ion batteries, and secondary batteries. Typically, the laminate is laminated with metal foils such as aluminum foil and a heat seal layer. The thickness of the film is preferably 5 to 75 μm, more preferably 7 to 50 μm. Heat-sealable film: Examples include lamination with a heat-seal layer such as polyethylene, polypropylene, or copolyester. The thickness of the heat-seal layer is preferably 5 to 100 μm, more preferably 10 to 70 μm. The thickness of the substrate film is preferably 5 to 75 μm, more preferably 7 to 50 μm. For these laminations, adhesives such as isocyanate curing type, epoxy curing type, and radiation curing type can be used.

[0131] Heat-shrinkable polyester film: Examples include beverage bottle labels, beverage can labels, cap seals, packaging for lidded containers, and shrink packaging. In these applications, in order to adjust the heat shrinkage characteristics, it is preferred to mix other polyesters and copolyester resins to form a film. Examples of other polyesters include tetramethylene terephthalate and trimethylene terephthalate. Examples of copolyesters include ethylene terephthalate isophthalate copolymers, ethylene butylene terephthalate copolymers, ethylene glycol 2,2-dimethylpropylene glycol terephthalate copolymers (a material in which neopentyl glycol is added to the diol component), ethylene glycol 2,2'-oxydiethanol copolymers (a material in which diethylene glycol is added to the diol component), and ethylene glycol 1,4-cyclohexanedimethanol terephthalate copolymers (a material in which 1,4-cyclohexanedimethanol is added to the diol component). Polyesters obtained by copolymerizing these with other components are preferred. The thickness of the heat shrinkable polyester film is preferably 5 to 50 μm, and more preferably 7 to 40 μm. The heat shrinkage of the heat-shrinkable polyester film is preferably 20 to 75%, more preferably 30 to 70%, and further preferably 35 to 67%. The heat shrinkage is: after hot water immersion at 95°C for 10 seconds, (length before hot water immersion - length after hot water immersion) / length before hot water immersion × 100 = shrinkage (%).

[0132] The polyester film can also be made by mixing and stretching the polyester resin with an incompatible resin such as polypropylene, polymethylpentene, polystyrene, etc. to form a void-containing film. At this time, the incompatible resin is preferably 3 to 25% by mass relative to the total resin amount constituting the film, and more preferably 5 to 15% by mass. The void-containing film can also be a multilayer structure with layers of different compositions, and the thickness of the void-containing film is preferably 10 to 300 μm, and more preferably 20 to 200 μm. The apparent specific gravity of the void-containing film is preferably 0.8 to 1.3, more preferably 0.9 to 1.2, and further preferably 0.95 to 1.15. In addition, various pigments such as titanium oxide, barium sulfate, and carbon can be added to produce white, black, or other colored films. These films are preferably used for labels, printing films that replace paper, light reflective films, circuit substrates, cards, tags, and the like.

[0133] Furthermore, polyimide, polyamideimide, polyamide, polyphenylene sulfide, polyphenylene sulfone, polyphenylene ether, etc. may be added as modified polyester film. In this case, the modified resin other than polyester is preferably 0.5 to 20% by mass, more preferably 1 to 15% by mass, and further preferably 2 to 10% by mass relative to the total resin amount constituting the film.

[0134] This application claims the benefit of priority based on Japanese Patent Application No. 2022-130153 filed on August 17, 2022. The entire contents of the specification of Japanese Patent Application No. 2022-130153 filed on August 17, 2022 are incorporated herein by reference. Example

[0135] The present invention will be described below by way of examples, but the present invention is not limited to these examples at all.

[0136] (1) Intrinsic viscosity (IV) About 3 g of the sample was freeze-pulverized, dried at 140°C for 15 minutes, and then 0.20 g was weighed and stirred at 100°C for 60 minutes using 20 ml of a mixed solvent of 1,1,2,2-tetrachloroethane and p-chlorophenol at a mass ratio of 1:3. After cooling to room temperature, the sample was filtered through a glass filter. The temperature was adjusted to 30°C, and the falling time of the sample and the solvent was calculated using an Ubbelohde viscometer (manufactured by Lihe Co., Ltd.), and the intrinsic viscosity [η] was calculated by the following formula. [η]=(-1+√(1+4K'ηSp)) / 2K'C ηSp=(τ-τ0)τ0 in, [η]: Intrinsic viscosity (dl / g) ηSp: Specific viscosity (-) K': Huggins constant (= 0.33) C: Concentration (=1g / dl) Falling time Falling time (sec) τ: Sample drop time (sec) τ0: solvent falling time (sec)

[0137] (2) Content of the specified metal element in the sample The polyester resin was weighed in a platinum crucible, carbonized in an electric heating furnace, and then ashed in a muffle furnace at 550°C for 8 hours. The ashed sample was dissolved in 1.2M hydrochloric acid to prepare a sample solution. The prepared sample solution was measured under the following conditions, and the concentrations of antimony and aluminum in the polyester resin were determined by high-frequency inductively coupled plasma emission spectrometry. Device: CIROS-120 manufactured by SPECTRO Plasma output: 1400W Plasma gas: 13.0L / min Auxiliary gas: 2.0L / min Nebulizer: Cross-flow nebulizer Spray chamber: Cyclone spray chamber Measurement wavelength: 167.078nm

[0138] (3) Phosphorus content in polyester resin 0.2 g of polyester resin was wet decomposed with 3 mL of 97% by mass sulfuric acid, 3 mL of 60% by mass nitric acid, and 0.5 mL of 60% by mass perchloric acid, and then neutralized with aqueous ammonia. 0.3 mL of 2% by mass ammonium molybdate and 0.3 mL of 0.5% by mass hydrazine sulfate were added to the prepared solution, and the absorbance at a wavelength of 830 nm was measured using an ultraviolet visible spectrophotometer (manufactured by Shimadzu Corporation, UV-1700). The concentration of phosphorus in the polyester resin was determined based on a pre-made calibration curve. In addition, the sample amount of the polyester resin can be adjusted in accordance with the concentration of phosphorus in the polyester resin.

[0139] (4) Content of dicarboxylic acid component and diol component in PET 20 mg of the polyester resin was dissolved in 0.6 ml of a mixed solvent of heavy hexafluoroisopropanol and deuterated chloroform at a ratio of 1:9 (volume ratio), and the mixture was centrifuged. Thereafter, the supernatant was collected and subjected to H-NMR measurement under the following conditions. Apparatus: Fourier transform nuclear magnetic resonance apparatus (manufactured by BRUKER, AVANCENEO600) 1H resonance frequency: 600.13MHz Lock solvent: deuterated chloroform Tipping angle: 30° Data acquisition time: 4 seconds Delay time: 1 second Measurement temperature: 30℃ Total times: 128 times

[0140] (5) Contents of dicarboxylic acid components and diol components in BHET The chemically recovered BHET was dissolved in heavy methanol and subjected to H-NMR measurement under the following conditions. Apparatus: Fourier transform nuclear magnetic resonance apparatus (manufactured by BRUKER) 1H resonance frequency: 500.13MHz Locking solvent: heavy methanol Tipping angle: 45° Data acquisition time: 4 seconds Delay time: 1 second Measurement temperature: 27℃ Total times: 36 times

[0141] (6) Heat shrinkage The polyester film was sampled into 10mm wide and marked with lines at intervals of 200mm. After measuring the intervals between the (L0) lines, the film was sandwiched between papers and placed in a hot air oven controlled at 150°C. After treatment for 30 minutes, it was taken out and the intervals between the (L) lines were measured. The heat shrinkage was calculated according to the following formula. In addition to taking samples in both the longitudinal and transverse directions for measurement, the calculation was based on JIS C2318. Thermal shrinkage (%) = {(L0-L) / L0} × 100 The heat shrinkage in MD direction is shown in Table 3.

[0142] (7)Lamination strength The biaxially stretched polyester film was laminated to a polyethylene film ("L4102" manufactured by Toyobo Co., Ltd.) having a thickness of 40 μm by dry lamination using a urethane adhesive (manufactured by Toyo-Morton Co., Ltd., TM569, CAT10L, and ethyl acetate mixed in a mass ratio of 33.6:4.0:62.4). The laminate was aged at 40°C for 4 days to obtain a laminate for lamination strength evaluation. The lamination conditions were as follows: a line speed of 20 m / min, a drying temperature of 80°C, and a coating amount of 3 g / m 2 The laminate was cut into pieces of 15 mm in width and 200 mm in length as test pieces, and the peel strength (N / 15 mm) on the bonding surface between the untreated surface of the polyester film and the polyolefin resin layer was measured using the "TensilonUMT-II-500" manufactured by Toyo Baldwin Co., Ltd. at a temperature of 23°C and a relative humidity of 65%. In addition, the tensile speed was set to 20 cm / min and the peeling angle was set to 180 degrees.

[0143] (8) Adhesion A UV-curable resin layer with a thickness of 5 μm was provided on the easy-adhesive layer of the polyester film. On the UV-curable resin layer, a cutter guide with a gap of 2 mm was used to penetrate the UV-curable resin layer and cut out 100 square scratches reaching the substrate film. Then, a transparent tape (Nichiban, No. 405; 24 mm wide) was pasted to the square scratch surface and rubbed with a roller to make it completely close. After that, the transparent tape was peeled off vertically from the UV-curable resin layer of the laminated polyester film 5 times, and the number of squares peeled off from the UV-curable resin layer of the laminated polyester film was visually counted, and the close adhesion between the UV-curable resin layer and the substrate film was obtained from the following formula. In addition, among the squares, the partially peeled squares were also counted as peeled squares and graded according to the following criteria. Adhesion (%) = (1-number of peeled squares / 100) × 100 ○: 80-100% △: 50~79% ×: 0~49%

[0144] (9) Rigidity The polyester film (thickness 18 μm) was cut into 20 cm×20 cm and crushed by hand to evaluate the rigidity. ◯: No difference was felt from the film of Reference Example 1 (thickness 18 μm). △: The rigidity is slightly low. ×: The rigidity is felt to be low.

[0145] (10) Area ratio of the region with molecular weight below 1000 After placing 10g of polyester film in a 30mL medicine bottle, weigh it. Add a mixed solution of chloroform / hexafluoroisopropanol (HFIP) = 98 / 2 (volume ratio) to the medicine bottle and let it stand for 12 hours to dissolve the sample. Then, dilute it with chloroform / hexafluoroisopropanol (HFIP) = 98 / 2 (volume ratio) to prepare a 0.1% solution. Use a 0.45μm filter (GL chromatographic disk non-aqueous N type 13N manufactured by GL Sciences) to filter the 0.1% solution. For the filtrate, perform gel permeation chromatography (GPC) measurement under the following conditions. Chromatographic columns used: TSKgelSuperHM-H×2 and TSKgelSuperH2000 manufactured by Tosoh Corporation Column temperature: 40°C Mobile phase: Chloroform / HFIP=98 / 2 (volume ratio) Flow rate: 0.6mL / min Injection volume: 20 μL Detection: 254nm (UV-visible detector) Positive molecular weight: Monodisperse polystyrene (manufactured by Tosoh Corporation) Device: HLC-8300GPC manufactured by Tosoh Corporation In the molecular weight distribution curve obtained by GPC measurement, the area ratio of the region with a molecular weight of 1,000 or less is determined. In addition, usually in GPC analysis, the area outside the circle of the calibration curve is generally not included in the calculation range of the GPC analysis. However, in this analysis, in order to more accurately determine the area ratio of the region with a molecular weight of less than 1000, not only the area inside the circle of the calibration curve but also the area of ​​the GPC chromatogram (i.e., the total peak area) including the area outside the circle of the calibration curve was calculated.

[0146] (11) Acid value The film and the raw material polyester resin were measured by the following method. Sample preparation The film or raw polyester resin is crushed, vacuum dried at 70°C for 24 hours, and weighed using a balance in the range of 0.20±0.0005g. In addition, when measuring the acid value of each layer, a sample in which each layer is extruded as a single layer is prepared as a sample. Let the mass at this time be W (g). Add 10ml of benzyl alcohol and the weighed sample to the test tube, immerse the test tube in a benzyl alcohol bath heated to 205°C, and dissolve the sample while stirring with a glass rod. Set the samples with a dissolution time of 3 minutes, 5 minutes, and 7 minutes as A, B, and C respectively. Next, prepare the test tube again, add only benzyl alcohol, and process it in the same steps. Set the samples with a dissolution time of 3 minutes, 5 minutes, and 7 minutes as a, b, and c, respectively.

[0147] Titration Titrate with 0.04 mol / l potassium hydroxide solution (ethanol solution) with known factors in advance. Use phenol red as an indicator, and determine the titration amount (ml) of the potassium hydroxide solution when the color changes from yellow-green to light red. Set the titration amount of samples A, B, and C as XA, XB, and XC (ml). Set the titration amount of samples a, b, and c as Xa, Xb, and Xc (ml). Using the titration amounts XA, XB, and XC for each dissolution time, the titration amount V (ml) when the dissolution time is 0 minutes is calculated by the least square method. Similarly, using Xa, Xb, and Xc, the titration amount V0 (ml) is calculated. Next, the acid value is calculated according to the following formula. Carboxyl terminal concentration (eq / ton) = [(V-V0) × 0.04 × NF × 1000] / W NF: Factor of 0.04 mol / l potassium hydroxide solution

[0148] The preparation of the aluminum-containing ethylene glycol solution and the phosphorus-containing ethylene glycol solution is described below.

[0149] <Preparation of Aluminum-Containing Ethylene Glycol Solution> An equal amount (volume ratio) of ethylene glycol is charged into a mixing box with respect to a 20 g / L aqueous solution of basic aluminum acetate, and after stirring at room temperature (23°C) for several hours, water is distilled from the system while stirring at 50-90°C for several hours under reduced pressure (3 kPa), to prepare an aluminum-containing ethylene glycol solution s containing 20 g / L of aluminum compound.

[0150] <Preparation of Phosphorus-Containing Ethylene Glycol Solution t> As a phosphorus compound, Irganox 1222 (manufactured by BASF) was charged into a mixing tank together with ethylene glycol, and heat-treated at 175° C. for 150 minutes while stirring under nitrogen substitution to prepare a phosphorus-containing ethylene glycol solution t containing 50 g / L of the phosphorus compound.

[0151] (Preparation for chemical recovery of BHET) Chemically recycled BHET with the composition shown in Table 2 was prepared. The PET constituting the raw material was mainly recycled material A (with isophthalic acid copolymerization), recycled material B (without isophthalic acid copolymerization, with diethylene glycol copolymerization) from beverage bottles, and recycled material PET film (without isophthalic acid and diethylene glycol copolymerization), and the composition was adjusted by changing the ratio of each. In addition, even in the case of copolymerization without diethylene glycol, the by-product of ethylene glycol was contained to a certain extent.

[0152] [Table 2] TPA: Terephthalic acid IPA: Isophthalic acid EG: Ethylene glycol DEG: Diethylene glycol

[0153] Example 1 A 10L stainless steel autoclave with a stirrer was charged with CR-BHET1 in Table 2 as chemically recovered BHET, and a mixed solution prepared by mixing the aluminum-containing ethylene glycol solution s and the phosphorus-containing ethylene glycol solution t prepared in the above method and liquefying the mixture was added, and triethylamine was further added as an alkali agent. The mixed solution was prepared so that the aluminum element and the phosphorus element were 21 mass ppm and 58 mass ppm relative to the mass of the chemically recovered PET. The added molar ratio of the phosphorus element to the aluminum element was 2.41. After that, nitrogen was used for replacement, and the system temperature was raised to 278°C while stirring. During this period, the system pressure was slowly reduced to 0.2 kPa, and a polycondensation reaction was carried out under this condition to obtain chemically recycled PET (CR-PET1-A1). After that, the obtained polyester resin was extruded into strands and cut into pellets. The time from the start of heating to the end of the reaction was 180 minutes. Using the obtained chemically recycled PET, a biaxially stretched polyester film was produced according to the following film production methods 1 and 2.

[0154] Example 2 The same method as in Example 1 was followed except that the stirring speed was increased, the pressure was further set to 0.13 kPa, and the time from the start of the temperature increase to the end of the reaction was set to 150 minutes.

[0155] Example 3 The same method as in Example 1 was followed except that the stirring speed was increased, the pressure was further set to 0.1 kPa, the system temperature was set to 280° C., and the time from the start of the temperature increase to the end of the reaction was set to 130 minutes.

[0156] Example 4 The same method as in Example 1 was followed except that CR-BHET2 in Table 2 was used as the chemically recovered BHET.

[0157] Example 5 The same method as in Example 2 was followed except that CR-BHET2 in Table 2 was used as the chemically recovered BHET.

[0158] Example 6 The same method as in Example 3 was followed except that CR-BHET2 in Table 2 was used as the chemically recovered BHET.

[0159] Example 7 The same method as in Example 1 was followed except that CR-BHET3 in Table 2 was used as the chemically recovered BHET.

[0160] Example 8 The same method as in Example 3 was followed except that CR-BHET4 in Table 2 was used as the chemically recovered BHET.

[0161] Example 9 The same procedure as in Example 3 was carried out except that antimony trioxide was used as a catalyst so that the amount of antimony element was 210 ppm by mass based on the obtained polyester resin.

[0162] Comparative Example 1 The same procedure as in Example 3 was performed except that CR-BHET5 in Table 2 was used as the chemical recovery BHET.

[0163] Comparative Example 2 The same procedure as in Example 3 was performed except that CR-BHET6 in Table 2 was used as the chemical recovery BHET.

[0164] Comparative Example 3 The same procedure as in Example 1 was followed except that CR-BHET7 in Table 2 was used as the chemically recovered BHET, no alkali agent was added, the stirring speed was reduced, and the time from the start of the temperature increase to the end of the reaction was set to 240 minutes.

[0165] Reference Example 1 A 10L stainless steel autoclave equipped with a stirrer was charged with high-purity terephthalic acid and ethylene glycol in a molar amount twice that of the terephthalic acid, triethylamine was added to 0.4 mol% relative to the acid component, and an esterification reaction was performed while distilling water from the system at 245°C under a pressure of 0.25 MPa to obtain a mixture of BHET and oligomers. Thereafter, the same procedure as in Example 3 was followed.

[0166] Film production1 The chemically recycled PET was dried and fed into a twin-screw extruder to further prepare respective master batch pellets containing 0.3% amorphous silica with an average particle size of 1.5 μm. The obtained master batch pellets and the chemically recycled PET pellets were dried at 125° C. under reduced pressure for 8 hours to form a mixture of chemically recycled BHET / master batch = 90 / 10 (mass ratio), and the mixture was fed into an extruder of a film manufacturing device, melted and kneaded at 280° C. The melt extruded from the T-die was placed in close contact with a cooling roll, and as an unstretched film, it was continuously stretched 3.2 times in the longitudinal direction using a roll heated to 100° C. with a peripheral speed difference, and then the longitudinally stretched film was conducted to a tenter and stretched 3.8 times in the transverse direction at 120° C. Then, it was heat-set at 230° C., and after a 2% relaxation treatment in the width direction, it was cooled, and after a corona treatment on both sides, it was wound up to obtain a biaxially stretched polyester film with a thickness of 18 μm. The obtained film was used for evaluation of heat shrinkage, lamination strength, and rigidity.

[0167] Film manufacturing 2 In addition to feeding only chemically recycled PET into the extruder, the following coating agent was applied to one side of the longitudinally stretched sheet until the final film had a dry weight of 0.15 g / m 2 A biaxially stretched polyester film was obtained in the same manner as in Film Production 1 except that the thickness of the obtained film was 75 μm. The obtained film was used for evaluation of adhesion.

[0168] Coating agent Water 53.04 mass% Isopropyl alcohol 30.00 mass% Polyurethane resin 16.13 mass% (aqueous dispersion of a reaction product of 4,4-dicyclohexyl diisocyanate, dimethylolbutyric acid, and polyhexamethylene carbonate diol having a number average molecular weight of 2000, solid content concentration 40% by mass), Particle 1 0.71 mass% (silica gel with an average particle size of 40 nm, solid content concentration 40 mass%) Particle 2 0.07 mass% (silica gel with an average particle size of 450 nm, solid content concentration 40 mass%) Surfactant 0.05 mass% (silicone type, solid content concentration 100 mass%)

[0169] The results are shown in Table 3. Examples 1 to 3 and 9 have the same heat resistance (low heat shrinkage) and rigidity as the PET made from terephthalic acid and ethylene glycol in the reference example. Examples 4 to 8 are examples in which the copolymer component is increased, and there is a tendency for the heat resistance to decrease slightly. Some difference in rigidity was confirmed between Examples 4 and 8, but it does not constitute a problem. On the other hand, the heat resistance of Comparative Examples 1 to 3 decreases and the rigidity is also poor. Furthermore, the films of the examples showed little variation in copolymer composition, and did not require adjustment of conditions due to composition variation during film production, thereby achieving high productivity.

[0170] [Table 3]

[0171] (Manufacture of barrier films) On the corona treated surface of the film obtained by the film manufacturing method 1 in Example 3, a composite oxide layer of silicon dioxide and aluminum oxide is formed as an inorganic thin film layer by electron beam evaporation. As evaporation sources, 3 mm to 5 mm granular SiO2 (purity 99.9%) and Al2O3 (purity 99.9%) are used. The composition of the inorganic thin film layer is SiO2 / Al2O3 (mass ratio) = 60 / 40, and the film thickness is 13 nm. The water vapor permeability of the obtained laminated film was measured according to JIS-K7129-1992B method and was 0.45 g / m 2 ·day, showing excellent barrier properties.

[0172] (Manufacture of release film) A release film was obtained by coating a release layer coating liquid having the following composition on the film obtained by the film production method 1 except that the film thickness in Example 3 was 28 μm, and drying the coating liquid to obtain a release film.

[0173] (Mold release layer coating liquid solid content 1.0 mass%, surface tension: 27 mN / m, viscosity 5 mPa·s) ·Methyl ethyl ketone 57.93 parts by mass ·Toluene 40.00 parts by mass 1.75 parts by mass of acrylic resin solution (Polymer of 20 mol% of octadecyl methacrylate, 40 mol% of hydroxyethyl methacrylate, and 40 mol% of methyl methacrylate, weight average molecular weight 30,000, solid content 40%) · Cross-linking agent 0.25 parts by mass Hexamethoxymethylolmelamine, solid content 100%) ·Silicone release agent 0.05 parts by mass (Polyether-modified polydimethylsiloxane, TSF4446, solid content 100%, manufactured by Momentive) Acid catalyst (p-toluenesulfonic acid) 0.02 parts by mass

[0174] (Coating of ceramic green sheets) A composition consisting of the following materials was stirred and mixed, and dispersed for 60 minutes using a bead mill using glass beads having a diameter of 0.5 mm as a dispersion medium to obtain a ceramic slurry. ·Toluene 38.3 parts by mass · 38.3 parts by mass of ethanol Barium titanate (HPBT-1 manufactured by Fuji Titanium Co., Ltd.) 64.8 parts by mass Polyvinyl butyral (S-LEC (registered trademark) BM-S manufactured by Sekisui Chemical Co., Ltd.) 6.5 parts by mass · DOP (dioctyl phthalate) 3.3 parts by mass The slurry was applied onto the release surface of the release film using an applicator until the dried slurry had a thickness of 5 μm, and dried at 90° C. for 1 minute to form a ceramic green sheet on the release film. After drying, the release film was peeled off. The film of the present invention can be suitably used as a base film of a release film.

[0175] (Manufacturing of printed layer laminated film) The corona-treated surface of the film obtained by the film manufacturing method 1 in Example 3 was subjected to gravure printing with a dot ratio of 5% using a printing ink (Finestar R92 ink manufactured by Toyo Ink Co., Ltd.) / a diluent solvent (SL302 manufactured by Toyo Ink Co., Ltd.) = 77 / 23. The film of the present invention can be suitably used as a printing film.

[0176] (Manufacture of Adhesive Layer Laminated Film) On the easy-adhesive layer of the film obtained by manufacturing method 2 in Example 6, an adhesive layer coating liquid consisting of 100 parts of an acrylic adhesive (SK-Dyne 1491H manufactured by Soken Chemical Co., Ltd.), 0.9 parts of a curing agent (curing agent L-45 manufactured by Soken Chemical Co., Ltd.) and a diluent was applied and dried to form an adhesive layer with a thickness of 10 μm. The obtained laminated film can be used as a base film of a surface protective film or a process protective film. In addition, it can also be used as an adhesive laminated film for labels, etc.

[0177] (Manufacturing of void-containing films) To 70% by mass of the PET prepared in Example 7, 6% by mass of a polystyrene resin having a melt flow rate of 2.0 g / 10 minutes (Toporex 570-57U manufactured by Mitsui Toatsu Co., Ltd.), 6% by mass of a polypropylene resin having a melt flow rate of 1.7 g / 10 minutes (Noblen FO-50F manufactured by Mitsui Toatsu Co., Ltd.) and 18% by mass of a polymethylpentene resin having a melt flow rate of 8 g / 10 minutes (TPX, DX-845 manufactured by Mitsui Petrochemicals Co., Ltd.) were mixed in a pelletized form, supplied to a twin-screw extruder, and kneaded thoroughly. The strands were cooled and cut to produce a master pellet containing a void-forming agent.

[0178] In addition, 50% by mass of the PET prepared in Example 7 and 50% by mass of anatase-type titanium dioxide particles (manufactured by Fuji Titanium Co., Ltd., TA-300) having an average particle size of 0.3 μm were mixed and supplied to a vented twin-screw extruder for preliminary kneading. The molten resin was continuously supplied to a vented single-screw kneading machine, kneaded, and then extruded. The obtained strand was cooled and cut to produce a masterbatch containing titanium dioxide.

[0179] Next, 63% by mass of the PET prepared in Example 7, 25% by mass of the masterbatch containing the above-mentioned void-forming agent, and 12% by mass of the masterbatch were mixed and vacuum dried to obtain a film raw material. Next, the raw materials for the film were supplied to an extruder and melt-mixed at 280° C., and then the melt extruded from a T-die was brought into close contact with a cooling roll to prepare an unstretched film.

[0180] The obtained unstretched film was stretched 3.4 times using rollers with different circumferential speeds. The obtained uniaxially stretched film was introduced into a tenter, heated at 140°C, stretched 3.6 times in the transverse direction, fixed in width, heat treated at 230°C for 5 seconds, and further relaxed by 5% in the width direction at 210°C to obtain a 150 μm thick void-containing polyester film. The apparent specific gravity of the obtained void-containing polyester film was 1.05 according to the JIS K-7112 float-sink method.

[0181] (Manufacture of heat shrinkable film) 40% by mass of the PET prepared in Example 2, 50% by mass of a copolyester consisting of 100% by mole of terephthalic acid, 30% by mole of neopentyl glycol and 70% by mole of ethylene glycol, and 10% by mass of polybutylene terephthalate were mixed in a granular form, melt-mixed at 280°C, and the melt extruded from the T-die was adhered to a cooling roll as an unstretched film. Using a tenter, the unstretched film was preheated at 100°C for 10 seconds, stretched 4.0 times in the transverse direction at 80°C, and heat-treated at 80°C for 10 seconds to obtain a film with a thickness of 45 μm. The resulting film was cut into 10 cm × 10 cm, immersed in hot water at 95°C for 10 seconds, and when the heat shrinkage was measured, the shrinkage in the transverse direction was 60%, and the shrinkage in the longitudinal direction was 3%, showing excellent heat shrinkage characteristics. In addition, copolyester and polybutylene terephthalate are substances obtained without recovering raw materials derived from petroleum. Industrial Applicability

[0182] According to the present invention, in a film made of polyethylene terephthalate obtained from BHET obtained by chemical recycling as a raw material, a polyester film having stable characteristics while ensuring high adhesion can be used as a substrate film for various laminates, and further, it can be stably produced. The polyester film of the present invention can be used as a substrate film for various laminates. According to the preferred present invention, a polyester film having a reduced heat shrinkage (especially MD direction heat shrinkage) and a sense of rigidity while ensuring high adhesion can be made from polyethylene terephthalate obtained from BHET obtained by chemical recycling as a raw material.

Claims

1. A polyester film, characterized in that The raw material resin contains polyethylene terephthalate obtained by polycondensing a raw material containing bis(2-hydroxyethyl) terephthalate as a polyester resin decomposition component, wherein the polyethylene terephthalate satisfies the following (a) to (c), (a) the amount of terephthalic acid component structural units in the polyethylene terephthalate relative to the total polycarboxylic acid component structural units is 98.0 mol% or more and 99.98 mol% or less; (b) the amount of the ethylene glycol component structural units in the polyethylene terephthalate relative to the total polyol component structural units is 97.5 mol% or more and 99.3 mol% or less; (c) The amount of the diethylene glycol component structural units in the polyethylene terephthalate is 0.7 mol% or more and 2.5 mol% or less based on the total polyol component structural units.

2. The polyester film according to claim 1, wherein the polyethylene terephthalate further satisfies (d), (d) The amount of the isophthalic acid component structural units in the polyethylene terephthalate is 0.02 mol% or more and 2.0 mol% or less based on the total polycarboxylic acid component structural units.

3. The polyester film according to claim 1, wherein the value of [the total amount of polycarboxylic acid component structural units in the polyethylene terephthalate + the total amount of polyol component structural units in the polyethylene terephthalate - the amount of terephthalic acid component structural units in the polyethylene terephthalate - the amount of ethylene glycol component structural units in the polyethylene terephthalate] is less than 4.1 mol %. The polyester film according to claim 1 , further comprising an alkali agent. The polyester film according to claim 1 , which is a void-containing film. The polyester film according to claim 1 , which is a heat-shrinkable film. 7 . The polyester film according to claim 1 , wherein the polyethylene terephthalate contains an aluminum compound and a phosphorus compound.

8. A polyester film, characterized in that The polyester constituting the film contains polyethylene terephthalate obtained by polycondensing a raw material containing bis(2-hydroxyethyl)terephthalate as a polyester resin decomposition component as a raw material resin, and satisfies the following (a') to (c'), (a') the amount of terephthalic acid component structural units in the polyester constituting the film is 98.0 mol% or more and 99.98 mol% or less relative to the total polycarboxylic acid component structural units; (b') the amount of ethylene glycol component structural units in the polyester constituting the film is 97.5 mol% or more and 99.3 mol% or less relative to the total polyol component structural units; (c′) The amount of diethylene glycol component structural units in the polyester constituting the film is 0.7 mol% or more and 2.5 mol% or less based on the total polyol component structural units.

9. The polyester film according to claim 8, wherein the polyester constituting the film further satisfies (d'), (d′) The amount of the isophthalic acid component structural units in the polyester constituting the film is 0.02 mol% or more and 2.0 mol% or less based on the total polycarboxylic acid component structural units. 10 . The polyester film according to claim 8 , wherein the polyester constituting the film contains an aluminum compound and a phosphorus compound. 11 . A polyester film laminate comprising the polyester film according to claim 1 .

12. The polyester film laminate according to claim 11, comprising one or more selected from the group consisting of a printed layer, a radiation-curing resin layer, an inorganic layer, a barrier layer, a resin film layer different from polyester, a heat seal layer, a release layer and an adhesive layer.

13. A method for producing a polyester film, characterized in that: comprising the steps of (A) and (B) below, (A) a step of polymerizing bis(2-hydroxyethyl) terephthalate having the following properties (e), (f) and (g) obtained by depolymerizing polyethylene terephthalate to obtain polyethylene terephthalate; and (B) a step of producing a film using the polyethylene terephthalate resin obtained by polymerization as a raw material resin, (e) the amount of terephthalic acid component structural units in bis(2-hydroxyethyl)terephthalate relative to the total polycarboxylic acid component structural units is 98 mol% or more and 99.98 mol% or less; (f) the amount of ethylene glycol component structural units in bis(2-hydroxyethyl) terephthalate relative to the total polyol component structural units is 98.7 mol% or more and 99.9 mol% or less; (g) The amount of the diethylene glycol component structural unit in bis(2-hydroxyethyl)terephthalate is 0.1 mol% or more and 2.6 mol% or less based on the total polycarboxylic acid component structural units.

14. The method for producing a polyester film according to claim 13, wherein the bis(2-hydroxyethyl)terephthalate further satisfies the following property (h): (h) The amount of the isophthalic acid component structural units in bis(2-hydroxyethyl)terephthalate is 0.02 mol% or more and 2.0 mol% or less based on the total polycarboxylic acid component structural units. 15 . The method for producing a polyester film according to claim 13 , wherein the step (A) comprises adding an alkali agent. 16 . The method for producing a polyester film according to claim 13 , wherein the step (A) includes adding a catalyst containing at least one selected from the group consisting of antimony compounds, germanium compounds and aluminum compounds. 17 . The method for producing a polyester film according to claim 13 , wherein the step (A) is performed within 200 minutes.

18. The method for producing a polyester film according to claim 13 or 14, wherein the polyethylene terephthalate satisfies the following (a) to (c): (a) the amount of terephthalic acid component structural units in the polyethylene terephthalate relative to the total polycarboxylic acid component structural units is 98.0 mol% or more and 99.98 mol% or less; (b) the amount of the ethylene glycol component structural units in the polyethylene terephthalate relative to the total polyol component structural units is 97.5 mol% or more and 99.3 mol% or less; (c) The amount of the diethylene glycol component structural units in the polyethylene terephthalate is 0.7 mol% or more and 2.5 mol% or less based on the total polyol component structural units.

19. The method for producing a polyester film according to claim 18, wherein the polyethylene terephthalate further satisfies (d), (d) The amount of the isophthalic acid component structural units in the polyethylene terephthalate is 0.02 mol% or more and 2.0 mol% or less based on the total polycarboxylic acid component structural units.

20. The method for producing a polyester film according to claim 18, wherein the value of [the total amount of polycarboxylic acid component structural units in the polyethylene terephthalate + the total amount of polyol component structural units in the polyethylene terephthalate - the amount of terephthalic acid component structural units in the polyethylene terephthalate - the amount of ethylene glycol component structural units in the polyethylene terephthalate] is less than 4.1 mol %.

Citation Information

Patent Citations

  • Printed resin film, laminate comprising said printed resin film, packaging container comprising said laminate, and laminate comprising polyester film, and packaging container comprising said laminate

    JP2022028868A

  • Pharmaceutical preparation

    JP2022130153A

Cited By

  • Polyester material, thermal shrinkage film and preparation method and application thereof

    CN122080375A